Magnetic recording medium, tape cartridge, and magnetic recording / reproducing device
By designing a magnetic layer with a non-magnetic support and a strong magnetic powder in the magnetic recording medium, and adding a non-magnetic layer with a non-magnetic powder therebetween to control the chlorine content and iron content, the problem of degradation of electromagnetic conversion characteristics of the magnetic recording medium under severe conditions is solved, and better stability and performance maintenance are achieved.
Patent Information
- Application Number
- CN202411349421.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
After the existing magnetic recording medium is stored under severe conditions, the electromagnetic conversion characteristics are easily reduced and it is difficult to maintain excellent performance.
A magnetic layer having a non-magnetic support and a ferromagnetic powder is used, and a non-magnetic layer containing a non-magnetic powder is added between the two, and the chlorine content and iron content of the magnetic layer and the non-magnetic layer are controlled within a certain range to suppress deterioration of the magnetic layer.
It effectively suppresses the reduction of electromagnetic conversion characteristics after storage under severe conditions, and improves the stability and performance retention ability of the magnetic recording medium.
Smart Images

Figure BDA0005061919340000351 
Figure BDA0005061919340000361 
Figure BDA0005061919340000362
Abstract
Description
Technical Field
[0001] The present invention relates to a magnetic recording medium, a magnetic tape box and a magnetic recording and reproducing device. Background Art
[0002] As a magnetic recording medium, there is known a magnetic recording medium having a structure of a magnetic layer and a non-magnetic layer (for example, refer to Patent Documents 1 to 3).
[0003] Patent Document 1: Japanese Patent Application Publication No. 2020-144960
[0004] Patent Document 2: Japanese Patent Application Publication No. 2004-103067
[0005] Patent Document 3: Japanese Patent Application Publication No. 2005-267714
[0006] As the desired performance of the magnetic recording medium, excellent electromagnetic conversion characteristics can be cited. Regarding electromagnetic conversion characteristics, for example, in Japanese Patent Publication No. 2020-144960 (Patent Document 1), it is recorded that the electromagnetic conversion characteristics of the magnetic tape of the embodiment after repeated travel in an environment of temperature 23°C and relative humidity 45% are reduced less (refer to paragraph 0119, Table 1 and paragraph 0123 of Japanese Patent Publication No. 2020-144960 (Patent Document 1)). In contrast, the inventors believe that it is also assumed that the magnetic recording medium will be used after being stored under harsh conditions (e.g., stored in a high temperature environment, stored in a high humidity environment and / or stored for a long time) in the future. Summary of the invention
[0007] Therefore, an object of one embodiment of the present invention is to provide a magnetic recording medium having a magnetic layer and a non-magnetic layer and having little degradation in electromagnetic conversion characteristics after storage under severe conditions.
[0008] One embodiment of the present invention is as follows.
[0009] [1] A magnetic recording medium comprising a non-magnetic support and a magnetic layer containing ferromagnetic powder,
[0010] A non-magnetic layer containing non-magnetic powder is further provided between the non-magnetic support and the magnetic layer.
[0011] The total chlorine content of the magnetic layer and the non-magnetic layer was 30.0 mg / m 2 The following, and
[0012] The total iron content of the magnetic layer and the non-magnetic layer was 300.0 mg / m 2 the following.
[0013] [2] The magnetic recording medium according to [1], wherein
[0014] In a cross-sectional image obtained by photographing with a scanning electron microscope, the porosity of the nonmagnetic layer is 10.0% or less.
[0015] [3] The magnetic recording medium according to [1] or [2], wherein
[0016] The non-magnetic powder of the non-magnetic layer includes carbon black.
[0017] [4] The magnetic recording medium according to [3], wherein
[0018] The non-magnetic layer contains 50.0 mass % or more of carbon black based on the total amount of the non-magnetic powder.
[0019] [5] The magnetic recording medium according to any one of [1] to [4], wherein
[0020] The nonmagnetic layer has a thickness of 1.00 μm or less.
[0021] [6] The magnetic recording medium according to any one of [1] to [5], wherein
[0022] The non-magnetic support further has a back coating layer containing non-magnetic powder on a surface side opposite to a surface side having the non-magnetic layer and the magnetic layer.
[0023] [7] The magnetic recording medium according to any one of [1] to [6], which is a magnetic tape.
[0024] [8] The magnetic recording medium according to [1], wherein
[0025] In a cross-sectional image obtained by scanning electron microscope, the porosity of the non-magnetic layer is 10.0% or less.
[0026] The non-magnetic layer contains 50.0 mass % or more of carbon black based on the total amount of the non-magnetic powder.
[0027] The thickness of the non-magnetic layer is less than 1.00 μm.
[0028] On the surface side of the non-magnetic support body opposite to the surface side having the non-magnetic layer and the magnetic layer,
[0029] Also having a back coating layer comprising non-magnetic powder, and
[0030] The magnetic recording medium is a magnetic tape.
[0031] [9] A tape cassette comprising the magnetic tape described in [7] or [8].
[0032]
[10] A magnetic recording and reproducing device comprising the magnetic recording medium according to any one of claims [1] to [8].
[0033] Effects of the Invention
[0034] According to one aspect of the present invention, a magnetic recording medium having a magnetic layer and a non-magnetic layer and having little reduction in electromagnetic conversion characteristics after storage under harsh conditions can be provided. Furthermore, according to one aspect of the present invention, a magnetic tape cassette and a magnetic recording and reproducing device including the magnetic recording medium can be provided. DETAILED DESCRIPTION
[0035] [Magnetic recording media]
[0036] One embodiment of the present invention relates to a magnetic recording medium, which has a non-magnetic support and a magnetic layer containing ferromagnetic powder, and further has a non-magnetic layer containing non-magnetic powder between the non-magnetic support and the magnetic layer. The total chlorine content of the magnetic layer and the non-magnetic layer is 30.0 mg / m2 per unit area (hereinafter, also recorded as "chlorine content (magnetic layer + non-magnetic layer)". 2 The total iron content of the magnetic layer and the non-magnetic layer is 300.0 mg / m2 per unit area (hereinafter, also described as "iron content (magnetic layer + non-magnetic layer)"). 2 the following.
[0037] <Method for measuring chlorine content (magnetic layer + non-magnetic layer) and iron content (magnetic layer + non-magnetic layer)>
[0038] The above-mentioned “chlorine content (magnetic layer + non-magnetic layer)” and the above-mentioned “iron content (magnetic layer + non-magnetic layer)” in the present invention and this specification are obtained by the following method.
[0039] (1) A sample piece for measurement is cut out from a magnetic recording medium to be measured. The sample piece may have any size as long as it can be introduced into a fluorescent X-ray analysis apparatus.
[0040] (2) The cut sample piece is introduced into a fluorescent X-ray analyzer, and the Cl content is measured based on the peak area of the chlorine (Cl) element, and the Fe content is measured based on the peak area of the iron (Fe) element.
[0041] (3) After the measurement in (2) above, take out the sample sheet from the fluorescent X-ray analysis device, wipe and remove the magnetic layer and the non-magnetic layer with a solvent. The solvent used here can be any solvent that can remove the magnetic layer and the non-magnetic layer. Then, introduce the sample sheet into the fluorescent X-ray analysis device, measure the Cl amount based on the peak area of the Cl element, and measure the Fe amount based on the peak area of the Fe element. Thus, for the magnetic recording medium with a back coating layer, the total Cl amount of the back coating layer and the total Fe amount of the non-magnetic support are calculated. For the magnetic recording medium without a back coating layer, the Cl amount and Fe amount of the non-magnetic support are calculated.
[0042] (4) The “chlorine content (magnetic layer + non-magnetic layer)” and the “iron content (magnetic layer + non-magnetic layer)” were calculated by the following formulas.
[0043] Chloride content (magnetic layer + non-magnetic layer) (mg / m 2 ) = [the amount of Cl obtained in (2) above - the amount of Cl obtained in (3) above] / the area of the sample piece
[0044] Iron content (magnetic layer + non-magnetic layer) (mg / m 2 ) = [the amount of Fe obtained in (2) above - the amount of Fe obtained in (3) above] / the area of the sample piece
[0045] The inventors have repeatedly conducted in-depth research to provide a magnetic recording medium having a magnetic layer and a non-magnetic layer and having less reduction in electromagnetic conversion characteristics after storage under harsh conditions. As a result, it was newly discovered that the reduction in electromagnetic conversion characteristics after storage under harsh conditions can be suppressed based on the magnetic recording medium whose chlorine content (magnetic layer + non-magnetic layer) and iron content (magnetic layer + non-magnetic layer) are within the ranges described above. In this regard, the inventors speculate that the chlorine element and iron element contained in the magnetic layer and / or the non-magnetic layer may become the cause of the deterioration of the magnetic characteristics of the ferromagnetic powder contained in the magnetic layer, the film degradation of the magnetic layer, and / or the film degradation of the non-magnetic layer during storage under harsh conditions. In contrast, the inventors believe that in the magnetic recording medium whose chlorine content (magnetic layer + non-magnetic layer) and iron content (magnetic layer + non-magnetic layer) are within the ranges described above, the occurrence of such degradation can be suppressed, and as a result, the reduction in electromagnetic conversion characteristics after storage under harsh conditions can be suppressed. However, the present invention is not limited to the speculation described in this specification.
[0046] In contrast, in the previously shown Japanese Patent Publication No. 2020-144960 (Patent Document 1), Japanese Patent Publication No. 2004-103067 (Patent Document 2), and Japanese Patent Publication No. 2005-267714 (Patent Document 3), it is not suggested that the chlorine content (magnetic layer + non-magnetic layer) and the iron content (magnetic layer + non-magnetic layer) should be reduced.
[0047] <Chlorine content (magnetic layer + non-magnetic layer)>
[0048] From the viewpoint of suppressing the decrease in electromagnetic conversion characteristics after storage under severe conditions, the chlorine content (magnetic layer + non-magnetic layer) of the magnetic recording medium is 30.0 mg / m 2 Below, preferably 28.0 mg / m 2 Below, more preferably 25.0 mg / m 2 Below, 20.0mg / m 2 Below, 15.0mg / m 2 Below, 10.0mg / m 2 The chlorine content of the magnetic recording medium (magnetic layer + non-magnetic layer) can be, for example, 0.0 mg / m 2 Above, more than 0.0mg / m 2 , 1.0mg / m 2 Above, 2.0mg / m 2 Above, 3.0mg / m 2 Above 4.0mg / m 2 Above or 5.0 mg / m 2 From the viewpoint of suppressing the reduction in electromagnetic conversion characteristics after storage under severe conditions, the chlorine content (magnetic layer + non-magnetic layer) of the magnetic recording medium is preferably as low as possible.
[0049] <Iron content (magnetic layer + non-magnetic layer)>
[0050] From the viewpoint of suppressing the decrease in electromagnetic conversion characteristics after storage under severe conditions, the iron content of the magnetic recording medium (magnetic layer + non-magnetic layer) is 300.0 mg / m 2 200.0 mg / m2 or less, preferably 280.0 mg / m2 or less, and more preferably 250.0 mg / m2 or less. 2 Below, 200.0mg / m 2 Below, 150.0mg / m 2 Below, 100.0mg / m 2 The iron content of the magnetic recording medium (magnetic layer + non-magnetic layer) can be, for example, 0.0 mg / m 2 Above, more than 0.0mg / m 2 , 1.0mg / m 2 Above 5.0mg / m 2 Above, 10.0mg / m 2 Above, 20.0mg / m 2 Above, 30.0mg / m 2 Above 40.0mg / m 2 Above, 50.0mg / m2 Above, 60.0mg / m 2 Above 70.0mg / m 2 Above 80.0mg / m 2 Above or 90.0 mg / m 2 From the viewpoint of suppressing the reduction in electromagnetic conversion characteristics after storage under severe conditions, the magnetic recording medium preferably has a lower iron content (magnetic layer + non-magnetic layer).
[0051] Hereinafter, the above-mentioned magnetic recording medium will be described in further detail.
[0052] <Thickness of Each Layer and Non-magnetic Support>
[0053] The magnetic recording medium has the non-magnetic layer and the magnetic layer, and in one embodiment, can also have a back coating layer containing non-magnetic powder on the surface side of the non-magnetic support body opposite to the surface side having the non-magnetic layer and the magnetic layer. In another embodiment, the magnetic recording medium can be a magnetic recording medium without the back coating layer.
[0054] The thickness of the magnetic layer can be optimized according to the saturation magnetization of the magnetic head used, the head gap length, the frequency band of the recording signal, etc. From the perspective of high-density recording, the thickness of the magnetic layer is preferably less than 100nm, more preferably 10 to 100nm, and further preferably 20 to 90nm. The magnetic layer can have at least one layer, or the magnetic layer can be separated into two or more layers with different magnetic properties, and structures related to known multi-layer magnetic layers can be applied. The thickness of the magnetic layer when separated into two or more layers is set to the total thickness of these layers. In this regard, the same is true when other layers are separated into two or more layers.
[0055] From the viewpoint of high capacity of the magnetic recording medium, the thickness of the non-magnetic layer is preferably less than 1.00 μm, more preferably less than 0.80 μm, and further preferably less than 0.60 μm. Furthermore, from the viewpoint of the ease of uniformly coating the non-magnetic layer forming composition, the thickness of the non-magnetic layer is preferably more than 0.05 μm, more preferably more than 0.07 μm, and further preferably more than 0.10 μm. Typically, the non-magnetic layer can be a layer thicker than the magnetic layer (for example, the thickness of the non-magnetic layer is more than 2 times, more than 3 times, more than 4 times, or more than 5 times the thickness of the magnetic layer). Therefore, it can be said that the contribution of the magnetic layer components to the chlorine content (magnetic layer + non-magnetic layer) and the iron content (magnetic layer + non-magnetic layer) is negligible.
[0056] The thickness of the back coat layer is preferably 0.90 μm or less, more preferably in the range of 0.10 to 0.70 μm.
[0057] The thickness of the non-magnetic support is, for example, in the range of 2.0 to 80.0 μm, preferably in the range of 2.0 to 50.0 μm, and more preferably in the range of 2.0 to 10.0 μm.
[0058] <Nonmagnetic Layer>
[0059] (Porosity of non-magnetic layer)
[0060] From the viewpoint of improving electromagnetic conversion characteristics by increasing the saturation magnetic flux density Bm of the magnetic layer, the porosity of the non-magnetic layer of the magnetic recording medium is preferably 20.0% or less, and more preferably 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, and 5.0% or less. And, for example, from the viewpoint of formability in a rolling process, the porosity of the non-magnetic layer is preferably 0.8% or more, more preferably 1.0% or more, further preferably 1.2% or more, further preferably 1.5% or more, and further preferably 2.0% or more.
[0061] The present inventors presume as follows why the saturation magnetic flux density Bm of the magnetic layer can be increased by reducing the void ratio of the nonmagnetic layer.
[0062] The composition for forming the non-magnetic layer usually contains a binder. Although it is preferred to adsorb the binder on the particle surface of the non-magnetic powder as much as possible from the viewpoint of improving the dispersibility of the non-magnetic powder in the non-magnetic layer and improving the film strength of the non-magnetic layer, it is generally believed that the total amount is not adsorbed. Therefore, it is speculated that in the non-magnetic layer, the non-adsorbed binder component that can be free exists in a state mixed with the adsorbed binder component. It is believed that the non-adsorbed binder component of the non-magnetic layer penetrates into the inside of the magnetic layer through the gap between the non-magnetic powder and the adsorbed binder component during the manufacturing process of the magnetic recording medium. Therefore, if the non-magnetic component of the magnetic layer increases, the ratio of the ferromagnetic powder in the volume of the magnetic layer will decrease. It is speculated that this will become the reason for the reduction of the saturation magnetic flux density Bm of the magnetic layer. Therefore, the inventors believe that if the porosity of the non-magnetic layer is reduced, the saturation magnetic flux density Bm of the magnetic layer can be increased as a result.
[0063] In the present invention and this specification, the porosity of the nonmagnetic layer is a value obtained from a cross-sectional image obtained using a scanning electron microscope (SEM). Hereinafter, a method for obtaining the porosity of the nonmagnetic layer will be described.
[0064] (1) Preparation of samples for cross-sectional observation
[0065] A sample for cross-sectional observation is prepared by cutting out a randomly specified position of the magnetic recording medium to be measured. The sample for cross-sectional observation is prepared by using gallium ions (Ga + The specific example of this production method is as follows.
[0066] (i) A sample of the magnetic recording medium having a size of 10 mm in the width direction and 10 mm in the length direction was cut using a razor.
[0067] A protective film was formed on the surface of the magnetic layer of the cut sample to obtain a sample with a protective film. The protective film was formed by the following method.
[0068] A platinum (Pt) film (30 nm thick) was formed on the surface of the magnetic layer of the sample by sputtering. Sputtering of the platinum film was performed under the following conditions.
[0069] (Sputtering conditions of platinum film)
[0070] Target: Pt
[0071] Vacuum degree in the sputtering chamber: below 7Pa
[0072] Current value: 15mA
[0073] A carbon film with a thickness of 100 to 150 nm was further formed on the sample with the platinum film produced above. The FIB (focused ion beam) apparatus used in the following (ii) was used to generate a carbon film using gallium ions (Ga + ) beam CVD (Chemical vapor deposition) mechanism to form the carbon film.
[0074] (ii) The sample with the protective film prepared in (i) above was subjected to a FIB apparatus using gallium ions (Ga + ) beam FIB processing was performed to expose the cross section of the magnetic recording medium. The acceleration voltage in the FIB processing was set to 30 kV and the probe current was set to 1300 pA.
[0075] For example, the cross-sectional observation sample thus exposed is used for SEM observation for obtaining the porosity of the nonmagnetic layer and for SEM observation for obtaining the thickness of the magnetic layer described later.
[0076] (2) Determination of the nonmagnetic layer
[0077] The prepared cross-sectional observation sample is observed by SEM, and a cross-sectional image (SEM image) is taken. As a scanning electron microscope, a field emission scanning electron microscope (FE (Field Emission)-SEM) is used. For example, FE-SEM S4800 manufactured by Hitachi, Ltd. can be used, and this FE-SEM is used in the following examples and comparative examples.
[0078] For the SEM image, in the same cross-sectional observation sample, (i) in a manner that the photographing range is not repeated, (ii) in a manner that the outermost surface on the magnetic layer side (magnetic layer surface) is included in the SEM image, and (iii) the entire area in the thickness direction of the cross-sectional observation sample (i.e., the area from the outermost surface on the magnetic layer side to the outermost surface on the other side) is included in the SEM image, or in a manner that the entire thickness direction of the cross-sectional observation sample is not included in the SEM image, the cross-sectional observation sample is selected in a manner that the proportion of the photographed part relative to the total image area of the SEM image is 80 to 100% on an area basis, and except for this point, shooting is performed at randomly selected positions to obtain a total of 10 images.
[0079] The above-mentioned SEM image is a secondary electron image (SE (secondary electron) image) taken at an acceleration voltage of 5 kV, a photographic magnification of 50,000 times, and a size of 960 pixels (pixels) in vertical direction and 1280 pixels in horizontal direction.
[0080] The captured SEM image is read into WinROOF manufactured by MITANI CORPORATION as image processing software, and the portion (measurement area) of the non-magnetic layer in the SEM image is selected. When the measurement area is selected, the length in the width direction of the measurement area is set to the total width of the captured SEM image. The "width direction" recorded about the SEM image refers to the width direction in the sample for cross-sectional observation captured. The width direction in the sample for cross-sectional observation refers to the width direction in the magnetic recording medium in which the sample is sheared. Regarding the above content, it is also the same in the thickness direction.
[0081] The interface between the magnetic layer and the non-magnetic layer is determined in the thickness direction by the following method. The SEM image is digitized to produce image brightness data in the thickness direction (including three components: coordinates in the thickness direction, coordinates in the width direction, and brightness). In the digitization, the SEM image is divided into 1280 in the width direction and processed with 8-bit brightness to obtain data of 256 tones, and the image brightness of each divided coordinate point is converted into a predetermined tone value. Then, in the obtained image brightness data, the average value of the brightness in the width direction at each coordinate point in the thickness direction is taken on the vertical axis (that is, the average value of the brightness at each coordinate point divided by 1280) and the coordinates in the thickness direction are taken on the horizontal axis to produce a brightness curve. The produced brightness curve is differentiated to produce a differential curve, and the coordinates of the boundary between the magnetic layer and the non-magnetic layer are determined from the peak position of the produced differential curve. The position on the SEM image corresponding to the determined coordinates is set as the interface between the magnetic layer and the non-magnetic layer. In the case where the SEM image contains a non-magnetic support body portion, the interface between the non-magnetic layer and the non-magnetic support body is determined. For example, in a coated magnetic recording medium, the interface between the non-magnetic layer and the non-magnetic support can be clearly identified compared to the interface between the magnetic layer and the non-magnetic layer. Therefore, the interface between the non-magnetic layer and the non-magnetic support can be determined by visually observing the SEM image. However, it can also be determined using a brightness curve in the same manner as described above. In the case where the SEM image does not include a portion of the non-magnetic support, the entire region in the thickness direction of the non-magnetic layer portion is determined as the non-magnetic layer from the interface between the determined magnetic layer and the non-magnetic layer (i.e., the surface of the non-magnetic layer). On the other hand, in the case where the non-magnetic support portion is included in the SEM image, the entire region from the interface between the determined magnetic layer and the non-magnetic layer (i.e., the magnetic layer side surface of the non-magnetic layer) and the interface between the non-magnetic layer and the non-magnetic support (i.e., the non-magnetic support side surface of the non-magnetic layer) is determined as the non-magnetic layer.
[0082] (3) Determination of voids in the non-magnetic layer and calculation of void fraction
[0083] The measurement area determined as the non-magnetic layer in (2) above was subjected to the sharpening process, which is a function of WinROOF manufactured by the above-mentioned image processing software MITANICORPORATION, and then subjected to noise elimination (4pixel 1 / 1280pixel 1) to emphasize the outline of the gap existing in the measurement area. In addition, the outline of the gap existing in the measurement area was manually selected, and then the outline and the part surrounded by the outline were binarized using the above-mentioned image processing software. At this time, the binarized area was less than 25nm 2 The part is not considered as a gap but as noise and is excluded from the selection. The binarized area is 25nm 2The above part is determined as voids. Next, the areas of the parts determined as voids are added together and used as the total area of voids. The void ratio is calculated according to the following formula. The void ratios are calculated for each of the 10 images, and their arithmetic average is used as the void ratio of the non-magnetic layer. In the following formula, if the units of the total void area and the area of the measurement area are the same, then nm can be used. 2 , can also be μm 2 , or other units.
[0084] Void ratio (%) = (total area of voids / area of measurement region) × 100
[0085] Among the voids existing in the measurement area, there may be a void that is partially located within the measurement area and the rest is located outside the measurement area. Regarding such voids, the area of the portion of the void located within the measurement area is used in calculating the total area of the voids when calculating the above-mentioned void ratio, and the area of the portion located outside the measurement area is not included in the calculation of the total area.
[0086] On the other hand, the thickness of the magnetic layer was obtained by the following method.
[0087] The cross-sectional observation sample prepared by the method described in (1) above is subjected to SEM observation, and a cross-sectional image (SEM image) is taken. As a scanning electron microscope, a field emission scanning electron microscope (FE-SEM) is used. For example, FE-SEM S4800 manufactured by Hitachi, Ltd. can be used, and this FE-SEM is used in the examples and comparative examples described below.
[0088] SEM images were taken at 10 randomly selected locations of the prepared cross-sectional observation sample so that the entire thickness direction of the nonmagnetic layer and at least a portion of the magnetic layer and at least a portion of the nonmagnetic support were included in the SEM image. In this way, a total of 10 SEM images were obtained.
[0089] The above SEM images are secondary electron images (SE images) taken at an acceleration voltage of 5 kV, a photographic magnification of 50,000 times, and 960 pixels in length and 1280 pixels in width. The interface between the magnetic layer and the non-magnetic layer is determined by the method described in (2) above. The surface of the magnetic layer is determined by visual observation.
[0090] At any position on each SEM image, the distance in the thickness direction between the interface between the magnetic layer and the non-magnetic layer determined by the above method and the surface of the magnetic layer is calculated, and the arithmetic average of the values obtained for 10 images is taken as the thickness of the magnetic layer. The thickness of other layers and non-magnetic support bodies other than the magnetic layer can also be calculated by the same method. Alternatively, the thickness of other layers can be calculated as the design thickness calculated according to the manufacturing conditions.
[0091] Improving the dispersibility of the non-magnetic powder in the non-magnetic layer may lead to a reduction in the porosity of the non-magnetic layer. In this regard, it is recorded in paragraph 0076 of Japanese Patent Publication No. 2020-144960 (Patent Document 1) as follows: In the non-magnetic layer containing carbon black as a non-magnetic powder, vinyl chloride resin is a binder that helps to improve the dispersibility of carbon black. However, a large amount of vinyl chloride resin is included in the non-magnetic layer, which will increase the value of the chlorine content (magnetic layer + non-magnetic layer) of the magnetic recording medium. In addition, in the embodiments of Japanese Patent Publication No. 2004-103067 (Patent Document 2) and Japanese Patent Publication No. 2005-267714 (Patent Document 3), α-iron oxide powder occupies most of the non-magnetic powder of the non-magnetic layer (refer to paragraph 0081 of Japanese Patent Publication No. 2004-103067 (Patent Document 2) and paragraph 0085 of Japanese Patent Publication No. 2005-267714 (Patent Document 3)). However, if the α-iron oxide powder occupies most of the non-magnetic powder of the non-magnetic layer, the iron content (magnetic layer + non-magnetic layer) of the magnetic recording medium will become higher. In contrast, in order to suppress the chlorine content (magnetic layer + non-magnetic layer) of the magnetic recording medium and the iron content (magnetic layer + non-magnetic layer) of the magnetic recording medium to a low level and reduce the porosity of the non-magnetic layer, it is preferred that the non-magnetic layer contain carbon black as described below and a binder as described below.
[0092] (Non-magnetic powder)
[0093] The non-magnetic layer is a layer containing at least non-magnetic powder. As the non-magnetic powder contained in the non-magnetic layer, only one non-magnetic powder may be used, or two or more non-magnetic powders may be used. As the non-magnetic powder, it is preferred to use at least carbon black, and more preferably to use carbon black having a pH in the range of 7.0 to 10.0. In the present invention and this specification, the pH of non-magnetic powders such as carbon black is set to a value measured according to the standard test method ASTM D1512.
[0094] Carbon black generally has a graphite structure, which is a fused polycyclic aromatic structure, and contains π electrons that can move freely in the structure. The inclusion of π electrons will show good conductivity. Therefore, carbon black can show the properties of an electron donor. When dispersed in water, it selectively adsorbs H+ ions among H+ ions and OH ions generated by the dissociation of water, resulting in residual OH ions, resulting in alkaline pH. This is because the main body of carbon black is the original graphite structure and it retains π electrons in abundance.
[0095] On the other hand, carbon black showing an acidic pH is also commercially available. In carbon black showing an acidic pH, oxygen is introduced into the structure by oxidation treatment. Oxygen is chemically bonded to carbon (C) to form functional groups showing acidity, such as hydroxyl groups and carboxyl groups. As the properties of the electron donor decrease due to this oxygen-carbon chemical bond, the pH decreases and the pH shown by the carbon black becomes an acidic pH. Therefore, it can be said that in carbon black showing an acidic pH, the original graphite structure undergoes chemical deterioration, thereby reducing the condensed polycyclic aromatic structure.
[0096] Based on the above reasons, the inventors believe that carbon black showing a neutral to alkaline pH, i.e., a pH in the range of 7.0 to 10.0, can have more fused polycyclic aromatic structures than carbon black showing an acidic pH. From the viewpoint of improving dispersibility, a binder preferably used in combination with carbon black showing a pH in the range of 7.0 to 10.0 will be described later.
[0097] Carbon black can be produced by, for example, a blast furnace process in which petroleum or coal-based oil is blown into high-temperature gas as a raw material to obtain carbon black by incomplete combustion. Carbon black produced by the blast furnace process is called furnace black. In addition, the following carbon blacks are also known as carbon blacks.
[0098] Lamp black produced by the lamp black process in which oil, pine, etc. are burned in a shallow dish; acetylene black produced by the acetylene black process in which acetylene gas is thermally decomposed; thermal black produced by the thermal black process in which other hydrocarbon gases are thermally decomposed; channel black produced by the channel black process in which natural gas, aromatic oil, etc. are partially oxidized.
[0099] As carbon black showing a neutral to alkaline pH, i.e., a pH in the range of 7.0 to 10.0, for example, carbon black selected from the group consisting of furnace black, lamp black, acetylene black, and thermal black can be used. In contrast, channel black tends to show an acidic pH. However, the method for producing the carbon black contained in the non-magnetic layer is not particularly limited.
[0100] From the viewpoint of reducing the porosity of the non-magnetic layer, the specific surface area of carbon black is preferably 280 m 2 / g or more, more preferably 300m 2 From the viewpoint of improving the dispersibility of carbon black in the non-magnetic layer, the specific surface area of carbon black is preferably 500 m 2 / g or less, more preferably 400m 2 / g or less. In the present invention and this specification, the specific surface area of various powders is the specific surface area calculated by the nitrogen adsorption method and the BET (Brunauer-Emmett-Teller) formula derived by Brunauer, Emmett and Teller in accordance with JIS K 6217-7:2013. The specific surface area of various powders used in the embodiments and comparative examples described below is the specific surface area measured for the raw material powder used in the preparation of the composition for forming each layer. However, it is also possible to remove the powder from the magnetic recording medium by a known method and calculate the specific surface area of the removed powder. In this regard, the same is true for the pH of the powder.
[0101] The proportion of carbon black in the non-magnetic powder of the non-magnetic layer relative to the total amount of the non-magnetic powder is preferably 50.0 mass % or more, more preferably 60.0 mass %, 70.0 mass %, 80.0 mass %, 90.0 mass % or more, and further preferably 100.0 mass % (i.e., the non-magnetic powder is only carbon black). In addition, the proportion of carbon black in the non-magnetic powder of the non-magnetic layer relative to the total amount of the non-magnetic powder may be 100.0 mass % or less, less than 100.0 mass %, less than 99.0 mass % or less than 95.0 mass %. The content rate (filling rate) of the non-magnetic powder in the non-magnetic layer relative to the total mass of the non-magnetic layer is preferably in the range of 50 to 90 mass %, more preferably in the range of 60 to 90 mass %.
[0102] As non-magnetic powders other than carbon black, inorganic powders or organic powders can be used. The average particle size of non-magnetic powders other than carbon black is preferably in the range of 10 to 200 nm, more preferably in the range of 10 to 100 nm. The specific surface area of non-magnetic powders other than carbon black can be, for example, 60 to 150 m 2 The pH of the non-magnetic powder other than carbon black may be, for example, in the range of 7.0 to 10.0.
[0103] For example, as inorganic powder, powders such as metal, metal oxide, metal carbonate, metal sulfate, metal nitride, metal carbide, metal sulfide can be cited. These non-magnetic powders can be obtained as commercial products, and can also be manufactured using known methods. For details, for example, reference can be made to paragraphs 0146 to 0150 of Japanese Patent Publication No. 2011-216149. As an example of non-magnetic powder, α-iron oxide powder (usually, also referred to as "iron red") can be cited. However, if α-iron oxide powder occupies most of the non-magnetic powder of the non-magnetic layer, the value of the iron content (magnetic layer + non-magnetic layer) of the magnetic recording medium will become high. Therefore, in the non-magnetic layer containing α-iron oxide powder, the proportion of α-iron oxide powder in the non-magnetic powder of the non-magnetic layer, relative to the total amount of the non-magnetic powder, is preferably less than 50.0 mass%, more preferably 40.0 mass% or less, and more preferably 30.0 mass% or less, 20.0 mass% or less, 10.0 mass% or less, 5.0 mass% or less, in that order, and further preferably 0.0 mass% (i.e., excluding α-iron oxide powder).
[0104] (Binder)
[0105] The magnetic recording medium can be a coated magnetic recording medium, and a binder can be included in the non-magnetic layer. The binder refers to one or more resins. In the present invention and this specification, the resin can be a homopolymer or a copolymer. As the binder of the non-magnetic layer, for example, a resin selected from polyurethane resin, polyester resin, polyamide resin, vinyl chloride resin, styrene, acrylonitrile, acrylic resin copolymerized with methyl methacrylate, cellulose resins such as nitrocellulose, epoxy resin, phenoxy resin, polyvinyl acetal, polyvinyl butyral, etc. can be used alone or a mixture of multiple resins. The average molecular weight of the resin used as the binder of the non-magnetic layer can be, for example, 5,000 or more and 200,000 or less or 10,000 or more and 200,000 or less as a weight average molecular weight. Unless otherwise specified, the weight average molecular weight and number average molecular weight in the present invention and this specification are values obtained by converting the values measured by gel permeation chromatography (GPC) using the following measurement conditions into polystyrene. The content of the binder may be, for example, 1.0 to 30.0 parts by mass relative to 100.0 parts by mass of the non-magnetic powder.
[0106] GPC apparatus: HLC-8120 (manufactured by TOSOH CORPORATION)
[0107] Column: TSK gel Multipore HXL-M (manufactured by TOSOH CORPORATION, 7.8 mm ID (Inner Diameter) × 30.0 cm)
[0108] Eluent: Tetrahydrofuran (THF)
[0109] From the viewpoint of improving dispersibility, a binder preferably used together with carbon black showing a pH in the range of 7.0 to 10.0 can be cited as a polyurethane resin having an aromatic ring structure. The present inventors believe that the polyurethane resin having an aromatic ring structure has high affinity and adsorption for carbon black showing a pH in the range of 7.0 to 10.0, and thus can contribute to improving the dispersibility of carbon black showing a pH in the above range.
[0110] As the polyurethane resin, polyurethane resins with various skeletons such as polyether carbamate, polyester carbamate, polycarbonate carbamate, and polyether ester carbamate can be cited. The polyurethane resin having an aromatic ring structure can be, for example, a polyurethane resin synthesized using an isocyanate having an aromatic ring structure as an isocyanate compound that becomes a raw material of the polyurethane. The carbamate group concentration of the polyurethane resin synthesized using an isocyanate having an aromatic ring structure is preferably 1.0 meq / g to 5.0 meq / g, and more preferably 1.5 meq / g to 4.5 meq / g. In the above-mentioned polyurethane resin having a carbamate group concentration of 1.0 meq / g or more, and further 1.5 meq / g or more, the aromatic ring skeleton derived from the isocyanate having an aromatic ring structure contained in the polyurethane chain is sufficient, and the affinity and adsorption to carbon black are good. Furthermore, the polyurethane resin having a carbamate group concentration of 5.0 meq / g or less, and further 4.5 meq / g or less, has high solubility in solvents generally used to prepare coated magnetic recording media, which can also help improve the dispersibility of carbon black. "eq" is equivalent, and is a unit that cannot be converted into SI units.
[0111] As the polyol and isocyanate compound used as the raw material of the polyurethane resin, there can be mentioned the long-chain diol, short-chain diol and diisocyanate compound described in the "Handbook of Polyurethane Resins" (edited by Keiichi Iwata, 1986 NIKKAN KOGYO SHIMBUN, LTD.). The shape of the polyurethane chain may be a straight chain or a polyurethane having a side chain structure and / or a branched structure.
[0112] In order to make the polyurethane resin have a side chain structure, a compound having two or more side chain structures and a functional group reactive with isocyanate in one molecule can be used. Examples of the compound having two or more side chain structures and a functional group reactive with isocyanate in one molecule include 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 2,2-dimethyl-1,3-propylene glycol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,2-dimethyl-3-hydroxypropyl-2',2'-dimethyl-3-hydroxypropionate, 2-n-butyl-2-ethyl-1,3-propylene glycol, 3-ethyl-1,5-pentanediol, 3-propyl-1,5-pentanediol, 2,2-diethyl-1,3-propylene glycol, 2-butyl, 2-ethyl v1,3-propanediol, 3-octyl-1,5-pentanediol, 3-phenyl-1,5vpentanediol, 2,5-dimethyl v3-sulfonate sodium-2,5-hexanediol, 1,3-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxyethyl)cyclohexane, 1,4-bis(hydroxypropyl)cyclohexane, 1,4-bis(hydroxymethoxy)cyclohexane, 1,4-bis(hydroxyethoxy)cyclohexane, 2,2-bis(4-hydroxymethoxycyclohexyl)propane, 2,2-bis(4-hydroxyethoxycyclohexyl)propane, bis(4-hydroxycyclohexyl)methane, 2,2-bis(4-hydroxycyclohexyl)propane, 3(4),8(9)-tricyclo[5.2.1.0 2,6 ] decanedimethanol, hydrogenated bisphenol A, ethylene oxide adduct of hydrogenated bisphenol A, propylene oxide adduct of hydrogenated bisphenol A, etc. As the compound having two or more side chain structures and functional groups that react with isocyanate in one molecule, 2,2-dimethyl-1,3-propanediol, 2,2-dimethyl-3-hydroxypropyl-2',2'-dimethyl-3-hydroxypropionate, 2-n-butyl-2-ethyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 3(4),8(9)-tricyclo[5.2.1.0 2,6 ] decanedimethanol, hydrogenated bisphenol A having an alicyclic skeleton, ethylene oxide adducts of hydrogenated bisphenol A, and propylene oxide adducts of hydrogenated bisphenol A, and hydrogenated bisphenol A having an alicyclic skeleton is more preferred.
[0113] In order to make the polyurethane resin have a branched structure, a small amount of trifunctional or higher alcohol can be used in addition to the diol compound during polyurethane polymerization. The trifunctional or higher alcohol is preferably trimethylolpropane, glycerol, pentaerythritol or their ethylene oxide adducts, propylene oxide adducts, etc.
[0114] For example, when the polyurethane resin is polyester urethane, it preferably has the following skeleton.
[0115] When the total of the acid component and the diol component of the polyester polyol is set to 100 mol%, it is preferred to contain more than 20 mol% of aromatic dibasic acid, and the remainder is composed of aliphatic dibasic acid and / or alicyclic dibasic acid. Moreover, the polyester polyol preferably contains 50 to 100 mol% of the total diol component by aliphatic diol components having an alkyl group with more than 1 carbon atom in the side chain. From the viewpoint of improving the dispersibility of carbon black and improving the travel durability of the magnetic recording medium, it is preferred to contain more than 20 mol% of aromatic dibasic acid. In addition, the molar ratio of dibasic acid / diol is not limited to 1 / 1, and it is also preferred that the diol component is excessive. The preferred range is 1 / 1 to 1 / 2.5.
[0116] Examples of the aromatic dibasic acid include terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc. Among these, isophthalic acid and phthalic acid are preferred from the viewpoint of achieving both dispersibility of carbon black and running durability of the magnetic recording medium.
[0117] Examples of the aliphatic diol component having an alkyl group having 1 or more carbon atoms in a side chain include 1,2-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 2-methyl-1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, 3-methyl-1,5-pentanediol, 2,2-dimethyl-3-hydroxypropyl-2',2'-dimethyl-3-hydroxypropionate, 2-butyl, 2-ethyl-1,3-propylene glycol, 2,2-diethyl-1,3-propylene glycol, etc. Among these, 2,2-dimethyl-1,3-propylene glycol, 2,2-diethyl-1,3-propylene glycol, 2-butyl, 2-ethyl-1,3-propylene glycol, and 2,2-dimethyl-3-hydroxypropyl-2',2'-dimethyl-3-hydroxypropionate are preferred.
[0118] Examples of other diol components used in the polyester polyol include aliphatic diols such as ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol, 1,3-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxyethyl)cyclohexane, 1,4-bis(hydroxypropyl)cyclohexane, 1,4-bis(hydroxymethoxy)cyclohexane, 1,4-bis(hydroxyethoxy)cyclohexane, 2,2-bis(4-hydroxymethoxycyclohexyl)propane, 2,2-bis(4-hydroxyethoxycyclohexyl)propane, bis(4-hydroxycyclohexyl)methane, 2,2-bis(4-hydroxycyclohexyl)propane, 3(4),8(9)-tricyclo[5.2.1.0 2 ,6Among these, 1,3-propylene glycol, 1,4-bis(hydroxymethyl)cyclohexane and 3(4),8(9)-tricyclo[5.2.1.0 2,6 ]Decanedimethanol.
[0119] The polyester polyol preferably has a number average molecular weight of 300 to 800 as calculated from the hydroxyl value measured by the method described in JIS K1557-1:2007 in order to obtain a polyurethane resin having high solubility in a solvent generally used for producing a coating type magnetic recording medium.
[0120] Examples of the aromatic isocyanate used for the synthesis of the polyurethane resin include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, m-phenylene diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, 2,6-naphthalene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 4,4'-diphenylene diisocyanate, 4,4'-diphenylene diisocyanate, 4,4'-diisocyanate diphenyl ether, 1,5-naphthalene diisocyanate, and m-xylene diisocyanate. Among these, 4,4'-diphenylmethane diisocyanate is more preferred.
[0121] As the short-chain diol component used for the synthesis of the polyurethane resin, reference can be made to the above descriptions regarding other diol components used in the polyester polyol and the above descriptions regarding compounds having two or more side chain structures and functional groups that react with isocyanate in one molecule. As specific examples of the short-chain diol, the short-chain diol used in the synthesis of the polyurethane resin A described later can also be cited. From the viewpoint of improving the solvent solubility of the unit in which the short-chain diol is bonded to the aromatic isocyanate, it is preferred to use a short-chain diol having a side chain structure in the synthesis of the polyurethane resin.
[0122] From the viewpoint of improving the dispersibility of carbon black showing a pH in the range of 7.0 to 10.0, the polyurethane resin preferably contains a sulfonate metal base in the skeleton. The sulfonate metal base has the function of being adsorbed on the basic site on the surface of carbon black. From the viewpoint of improving the dispersibility of carbon black showing a pH in the above range and improving the solvent solubility of the polyurethane resin, the sulfonate metal base content in the polyurethane resin is preferably in the range of 60 to 400 eq / ton. As a method for introducing the sulfonate metal base into the polyurethane resin, for example, there is a method of copolymerizing sodium 5-sulfoisophthalate or potassium 5-sulfoisophthalate in a polyester polyol or using a diol containing a sulfonate metal base.
[0123] The number average molecular weight of the polyurethane resin is preferably in the range of 5,000 to 100,000, more preferably in the range of 10,000 to 80,000. The synthesis method of the polyurethane resin may be any of a method of synthesizing the raw materials in a molten state and a method of synthesizing the raw materials by dissolving the raw materials in a solution. As a reaction catalyst, stannous octoate, dibutyltin dilaurate, triethylamine, etc. can be used. In addition, ultraviolet absorbers, hydrolysis inhibitors, antioxidants, etc. may be added before, during, or after the manufacture of the polyurethane resin.
[0124] The content of the polyurethane resin having an aromatic ring structure relative to the total amount of the binder in the non-magnetic layer is preferably 50.0 mass % or more, and more preferably 60.0 mass %, 70.0 mass %, 80.0 mass %, 90.0 mass %, 95.0 mass % or more, respectively, and further preferably 100.0 mass % (i.e., the binder in the non-magnetic layer is only the polyurethane resin having an aromatic ring structure).
[0125] As the binder of the non-magnetic layer, only one or more polyurethane resins having an aromatic ring structure may be used, or one or more polyurethane resins having an aromatic ring structure and one or more resins other than the polyurethane resin having an aromatic ring structure may be used. Vinyl chloride resin can increase the value of the chlorine content (magnetic layer + non-magnetic layer) of the magnetic recording medium, so when the binder of the non-magnetic layer contains vinyl chloride resin, it is preferably 50.0% by mass or less relative to the total amount of the binder of the non-magnetic layer, and more preferably 40.0% by mass or less, 30.0% by mass or less, 20.0% by mass or less, 10.0% by mass or less, 5.0% by mass or less, and further preferably 0.0% by mass (i.e., no vinyl chloride resin is contained).
[0126] In the non-magnetic layer, one or more other known additives can be appropriately selected from commercial products or produced by a known method according to desired properties and used in any amount. For additives that can be contained in the non-magnetic layer, reference can also be made to the description below.
[0127] In the present invention and this specification, the non-magnetic layer also includes a substantially non-magnetic layer containing non-magnetic powder and, for example, a small amount of ferromagnetic powder as an impurity or intentionally. Here, the substantially non-magnetic layer refers to a layer having a residual magnetic flux density of 10 mT or less, a coercive force of 1000 e or less, or a residual magnetic flux density of 10 mT or less and a coercive force of 1000 e or less. With respect to the unit Oe, 1 [kOe] = 10 6 / 4π[A / m]. The nonmagnetic layer preferably has no residual magnetic flux density and no coercive force.
[0128] <Magnetic layer>
[0129] (Strong magnetic powder)
[0130] As the ferromagnetic powder contained in the magnetic layer, a ferromagnetic powder known as a ferromagnetic powder used in the magnetic layer of various magnetic recording media can be used. As the ferromagnetic powder, from the viewpoint of improving the recording density, it is preferred to use a ferromagnetic powder with a small average particle size. From this point of view, the average particle size of the ferromagnetic powder is preferably 50 nm or less, more preferably 45 nm or less, further preferably 40 nm or less, further preferably 35 nm or less, further preferably 30 nm or less, further preferably 25 nm or less, further preferably 20 nm or less. On the other hand, from the viewpoint of magnetization stability, the average particle size of the ferromagnetic powder is preferably 5 nm or more, more preferably 8 nm or more, further preferably 10 nm or more, further preferably 15 nm or more.
[0131] Hexagonal ferrite powder
[0132] As a preferred specific example of the ferromagnetic powder, hexagonal ferrite powder can be cited. For details of the hexagonal ferrite powder, for example, reference can be made to paragraphs 0012 to 0030 of Japanese Patent Application Publication No. 2011-225417, paragraphs 0134 to 0136 of Japanese Patent Application Publication No. 2011-216149, paragraphs 0013 to 0030 of Japanese Patent Application Publication No. 2012-204726, and paragraphs 0029 to 0084 of Japanese Patent Application Publication No. 2015-127985.
[0133] In the present invention and this specification, "hexagonal ferrite powder" refers to a ferromagnetic powder in which the crystal structure of hexagonal ferrite is detected as the main phase by X-ray diffraction analysis. The main phase refers to the structure to which the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by X-ray diffraction analysis belongs. For example, in the case where the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by X-ray diffraction analysis belongs to the crystal structure of hexagonal ferrite, it is judged that the crystal structure of hexagonal ferrite is detected as the main phase. In the case where only a single structure is detected by X-ray diffraction analysis, the detected structure is regarded as the main phase. As constituent atoms, the crystal structure of hexagonal ferrite contains at least iron atoms, divalent metal atoms and oxygen atoms. Divalent metal atoms are metal atoms that can become divalent cations as ions, and examples include alkaline earth metal atoms such as strontium atoms, barium atoms, and calcium atoms, lead atoms, and the like. In the present invention and this specification, hexagonal strontium ferrite powder refers to hexagonal ferrite in which the main divalent metal atoms contained in the powder are strontium atoms, and hexagonal barium ferrite powder refers to hexagonal ferrite in which the main divalent metal atoms contained in the powder are barium atoms. The main divalent metal atoms refer to the divalent metal atoms that account for the largest proportion on an atomic % basis among the divalent metal atoms contained in the powder. However, the above-mentioned divalent metal atoms do not include rare earth atoms. The "rare earth atoms" in the present invention and this specification are selected from the group consisting of scandium atoms (Sc), yttrium atoms (Y) and lanthanide atoms. The lanthanide atom is selected from the group consisting of lanthanum atom (La), cerium atom (Ce), praseodymium atom (Pr), neodymium atom (Nd), promethium atom (Pm), samarium atom (Sm), europium atom (Eu), gadolinium atom (Gd), terbium atom (Tb), dysprosium atom (Dy), holmium atom (Ho), erbium atom (Er), thulium atom (Tm), ytterbium atom (Yb) and lutetium atom (Lu).
[0134] Hereinafter, hexagonal strontium ferrite powder which is one embodiment of the hexagonal ferrite powder will be described in more detail.
[0135] The activation volume of hexagonal strontium ferrite powder is preferably between 800 and 1500 nm. 3 The micronized hexagonal strontium ferrite powder showing the above-mentioned activation volume is suitable for preparing a magnetic recording medium having excellent electromagnetic conversion characteristics. The activation volume of the hexagonal strontium ferrite powder is preferably 800 nm. 3 Above, for example, it can also be 850nm 3 Furthermore, from the viewpoint of further improving the electromagnetic conversion characteristics, the activation volume of the hexagonal strontium ferrite powder is more preferably 1400 nm. 3 Below, more preferably 1300nm 3 Below, more preferably 1200nm 3Below, more preferably 1100nm 3 As for the hexagonal barium ferrite powder, the activation volume is also preferably within the above range.
[0136] The "activation volume" is a unit of magnetization reversal and is an indicator of the magnetic magnitude of a particle. The activation volume and the anisotropy constant Ku described in the present invention and this specification are values obtained by measuring the magnetic field scanning speed of the coercive force Hc measuring unit at 3 minutes and 30 minutes using a vibrating sample magnetometer (measuring temperature: 23°C ± 1°C) and using the following relationship between Hc and the activation volume V. The unit of the anisotropy constant Ku is 1erg / cc = 1.0×10 -1 J / m 3 .
[0137] Hc=2Ku / Ms{1-[(kT / KuV)ln(At / 0.693)] 1 / 2}
[0138] [In the above formula, Ku: anisotropy constant (unit: J / m 3 ), Ms: saturation magnetization (unit: kA / m), k: Boltzmann constant, T: absolute temperature (unit: K), V: activation volume (unit: cm 3 ), A: Spin precession frequency (unit: s -1 ), t: magnetic field reversal time (unit: s)]
[0139] As an index for reducing thermal fluctuation (in other words, improving thermal stability), the anisotropy constant Ku can be cited. The hexagonal strontium ferrite powder preferably has a value of 1.8×10 5 J / m 3 More preferably, Ku can be 2.0×10 5 J / m 3 Furthermore, the Ku of the hexagonal strontium ferrite powder can be, for example, 2.5×10 5 J / m 3 However, a higher Ku indicates higher thermal stability, which is more preferable, and therefore the value is not limited to the above-exemplified value.
[0140] The hexagonal strontium ferrite powder may contain rare earth atoms or may not contain rare earth atoms. When the hexagonal strontium ferrite powder contains rare earth atoms, it is preferred that the rare earth atoms are contained at a content (bulk content) of 0.5 to 5.0 atomic % relative to 100 atomic % of iron atoms. In one embodiment, the hexagonal strontium ferrite powder containing rare earth atoms may have a surface partiality of rare earth atoms. The "surface partiality of rare earth atoms" in the present invention and this specification means that the rare earth atom content relative to 100 atomic % of iron atoms in the solution obtained by partially dissolving the hexagonal strontium ferrite powder using acid (hereinafter referred to as "surface content of rare earth atoms" or simply "surface content" for rare earth atoms) and the rare earth atom content relative to 100 atomic % of iron atoms in the solution obtained by completely dissolving the hexagonal strontium ferrite powder using acid (hereinafter referred to as "bulk content of rare earth atoms" or simply "bulk content" for rare earth atoms) satisfy the following ratio:
[0141] The rare earth atom surface content / rare earth atom bulk content>1.0.
[0142] The rare earth atom content of the hexagonal strontium ferrite powder described below has the same meaning as the rare earth atom bulk content. In contrast, since partial dissolution using an acid dissolves the surface portion of the particles constituting the hexagonal strontium ferrite powder, the rare earth atom content in the solution obtained by partial dissolution refers to the rare earth atom content in the surface portion of the particles constituting the hexagonal strontium ferrite powder. The rare earth atom surface portion content ratio that satisfies "rare earth atom surface portion content / rare earth atom bulk content>1.0" indicates that the rare earth atoms in the particles constituting the hexagonal strontium ferrite powder are biased toward the surface portion (i.e., the amount present is greater than the interior). The surface portion in the present invention and this specification refers to a portion of the area from the surface of the particles constituting the hexagonal strontium ferrite powder toward the interior.
[0143] In the case where the hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atom content (bulk content) is preferably in the range of 0.5 to 5.0 atomic % relative to 100 atomic % of iron atoms. It is believed that the inclusion of rare earth atoms at a bulk content within the above range and the rare earth atoms being concentrated in the surface portion of the particles constituting the hexagonal strontium ferrite powder help to suppress the reduction in regeneration output during repeated regeneration. It is speculated that this is because the anisotropy constant Ku can be improved by the hexagonal strontium ferrite powder containing rare earth atoms at a bulk content within the above range and the rare earth atoms being concentrated in the surface portion of the particles constituting the hexagonal strontium ferrite powder. The higher the value of the anisotropy constant Ku, the more it can suppress the occurrence of the phenomenon known as thermal fluctuation (in other words, the more it can improve thermal stability). By suppressing the occurrence of thermal fluctuations, the reduction in regeneration output during repeated regeneration can be suppressed. It is presumed that the concentration of rare earth atoms in the surface layer of the hexagonal strontium ferrite powder particles contributes to stabilizing the spin of the iron (Fe) position in the crystal lattice of the surface layer, thereby improving the anisotropy constant Ku.
[0144] Furthermore, it is speculated that the use of hexagonal strontium ferrite powder with surface partiality of rare earth atoms as a ferromagnetic powder of the magnetic layer can also help to suppress the surface of the magnetic layer from being ground due to sliding with the magnetic head. In other words, it is speculated that the hexagonal strontium ferrite powder with surface partiality of rare earth atoms can also help to improve the travel durability of the magnetic recording medium. It is speculated that this is because the rare earth atoms are partial to the surface of the particles constituting the hexagonal strontium ferrite powder, which helps to improve the interaction between the particle surface and the organic substance (e.g., binder and / or additive) contained in the magnetic layer, and as a result, the strength of the magnetic layer is improved.
[0145] From the perspective of further suppressing the decrease in regeneration output during repeated regeneration and / or further improving the running durability, the rare earth atom content (bulk content) is more preferably in the range of 0.5 to 4.5 atomic %, further preferably in the range of 1.0 to 4.5 atomic %, and further preferably in the range of 1.5 to 4.5 atomic %.
[0146] The above-mentioned bulk content is the content obtained by completely dissolving the hexagonal strontium ferrite powder. In the present invention and this specification, unless otherwise specified, the content of atoms refers to the bulk content obtained by completely dissolving the hexagonal strontium ferrite powder. As rare earth atoms, the hexagonal strontium ferrite powder containing rare earth atoms may contain only one rare earth atom, or may contain two or more rare earth atoms. The above-mentioned bulk content when containing two or more rare earth atoms is obtained for the total of the two or more rare earth atoms. This is also the same for other components in the present invention and this specification. That is, unless otherwise specified, a certain component may be used in only one kind or in more than two kinds. The content or content when using more than two kinds is for the total of more than two kinds.
[0147] When the hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atoms contained may be any one or more of the rare earth atoms. Preferred rare earth atoms from the viewpoint of further suppressing the reduction of the regeneration output during repeated regeneration include neodymium atoms, samarium atoms, yttrium atoms and dysprosium atoms, more preferably neodymium atoms, samarium atoms and yttrium atoms, and still more preferably neodymium atoms.
[0148] In the hexagonal strontium ferrite powder having a surface partiality of rare earth atoms, the rare earth atoms only need to be partial to the surface of the particles constituting the hexagonal strontium ferrite powder, and the degree of partiality is not limited. For example, with respect to the hexagonal strontium ferrite powder having a surface partiality of rare earth atoms, the ratio of the surface content of rare earth atoms obtained by partial dissolution under the dissolution conditions described later to the bulk content of rare earth atoms obtained by complete dissolution under the dissolution conditions described later, "surface content / bulk content", exceeds 1.0 and may be greater than 1.5. "Surface content / bulk content" greater than 1.0 indicates that the rare earth atoms in the particles constituting the hexagonal strontium ferrite powder are partial to the surface (i.e., the amount present is greater than that in the interior). Furthermore, the ratio of the surface content of rare earth atoms obtained by partial dissolution under the dissolution conditions described later to the bulk content of rare earth atoms obtained by complete dissolution under the dissolution conditions described later, "surface content / bulk content", can be, for example, less than 10.0, less than 9.0, less than 8.0, less than 7.0, less than 6.0, less than 5.0, or less than 4.0. However, in the hexagonal strontium ferrite powder having surface partiality of rare earth atoms, the rare earth atoms only need to be partial to the surface of the particles constituting the hexagonal strontium ferrite powder, and the above-mentioned "surface content / bulk content" is not limited to the upper or lower limits exemplified.
[0149] The following describes the partial dissolution and complete dissolution of hexagonal strontium ferrite powder. Regarding the hexagonal strontium ferrite powder in the form of powder, the partially dissolved and completely dissolved sample powders are collected from the same batch of powder. On the other hand, for the hexagonal strontium ferrite powder contained in the magnetic layer of the magnetic recording medium, a part of the hexagonal strontium ferrite powder taken out from the magnetic layer is partially dissolved, and the other part is completely dissolved. When the hexagonal strontium ferrite powder is taken out from the magnetic layer, it can be carried out, for example, by the method described in paragraph 0032 of Japanese Patent Gazette No. 2015-91747.
[0150] The above-mentioned partial dissolution means that the hexagonal strontium ferrite powder is dissolved to the extent that the residue can be confirmed in the liquid with the naked eye at the end of the dissolution. For example, by partial dissolution, 10 to 20% by mass (with the whole particles as 100% by mass) of the particles constituting the hexagonal strontium ferrite powder can be dissolved. On the other hand, the above-mentioned complete dissolution means that the hexagonal strontium ferrite powder is dissolved to the extent that the residue can no longer be confirmed in the liquid with the naked eye at the end of the dissolution.
[0151] The above-mentioned partial dissolution and surface content rate are measured, for example, by the following method. However, the dissolution conditions such as the sample powder amount described below are merely examples, and any dissolution conditions that allow partial dissolution and complete dissolution can be adopted.
[0152] Place a container (e.g., a beaker) containing 12 mg of sample powder and 10 ml of 1 mol / L hydrochloric acid on a hot plate set at 70°C for 1 hour. Filter the obtained solution using a 0.1 μm membrane filter. Perform elemental analysis of the filtrate thus obtained using an inductively coupled plasma (IΛP; Inductively Coupled Plasma) analyzer. In this way, the surface content of rare earth atoms relative to 100 atomic % of iron atoms can be calculated. When multiple rare earth atoms are detected by elemental analysis, the total content of all rare earth atoms is taken as the surface content. This is also the same in the determination of bulk content.
[0153] On the other hand, the above-mentioned complete dissolution and block content rate are measured, for example, by the following method.
[0154] A container (e.g., a beaker) containing 12 mg of sample powder and 10 ml of 4 mol / L hydrochloric acid is placed on a hot plate set at 80°C for 3 hours. Then, the bulk content relative to 100 atomic % of iron atoms can be determined by performing the same steps as those for the determination of partial dissolution and surface content.
[0155] From the viewpoint of improving the regeneration output when reproducing data recorded in the magnetic recording medium, it is preferred that the mass magnetization σs of the ferromagnetic powder contained in the magnetic recording medium is high. In this regard, a hexagonal strontium ferrite powder containing rare earth atoms but not having surface partiality of rare earth atoms is observed to have a tendency of significantly reduced σs compared to a hexagonal strontium ferrite powder not containing rare earth atoms. In contrast, in order to suppress such a significant reduction in σs, it is also considered preferred to use a hexagonal strontium ferrite powder having surface partiality of rare earth atoms. In one embodiment, the σs of the hexagonal strontium ferrite powder can be 45A·m 2 / kg or more, and can also be 47A·m 2 / kg or more. On the other hand, from the viewpoint of noise reduction, σs is preferably 80A·m 2 / kg or less, more preferably 60A·m 2 / kg or less. σs can be measured using a known measuring device capable of measuring magnetic properties, such as a vibrating sample magnetometer. In the present invention and this specification, unless otherwise specified, the mass magnetization σs is a value measured at a magnetic field intensity of 15 kOe.
[0156] Regarding the content of constituent atoms of the hexagonal strontium ferrite powder (bulk content), the strontium atom content can be, for example, in the range of 2.0 to 15.0 atomic % relative to 100 atomic % of iron atoms. In one embodiment, the hexagonal strontium ferrite powder can be a powder in which the divalent metal atoms contained therein are only strontium atoms. Furthermore, in another embodiment, the hexagonal strontium ferrite powder can also contain one or more other divalent metal atoms in addition to strontium atoms. For example, barium atoms and / or calcium atoms can be contained. In the case of containing other divalent metal atoms in addition to strontium atoms, the barium atom content and the calcium atom content in the hexagonal strontium ferrite powder can be, for example, in the range of 0.05 to 5.0 atomic % relative to 100 atomic % of iron atoms, respectively.
[0157] As the crystal structure of hexagonal ferrite, magnetoplumbite type (also called "M type"), W type, Y type and Z type are known. Hexagonal strontium ferrite powder can adopt any crystal structure. The crystal structure can be confirmed by X-ray diffraction analysis. Hexagonal strontium ferrite powder can detect a single crystal structure or two or more crystal structures by X-ray diffraction analysis. For example, in one embodiment, hexagonal strontium ferrite powder can detect only M type crystal structure by X-ray diffraction analysis. For example, M type hexagonal ferrite is composed of AFe 12 O 19The composition formula is represented by . Here, A represents a divalent metal atom. When the hexagonal strontium ferrite powder is of M type, A is only a strontium atom (Sr) or when A contains multiple divalent metal atoms, the strontium atom (Sr) accounts for the largest proportion on an atomic % basis as described above. The divalent metal atom content of the hexagonal strontium ferrite powder is usually determined according to the type of crystal structure of the hexagonal ferrite and is not particularly limited. This is also the same for the iron atom content and the oxygen atom content. The hexagonal strontium ferrite powder contains at least iron atoms, strontium atoms and oxygen atoms, and may further contain rare earth atoms. Moreover, the hexagonal strontium ferrite powder may contain atoms other than these atoms, or may not contain atoms other than these atoms. As an example, the hexagonal strontium ferrite powder may contain aluminum atoms (A1). The content of aluminum atoms can be, for example, 0.5 to 10.0 atomic % relative to 100 atomic % of iron atoms. From the viewpoint of further suppressing the reduction of regeneration output during repeated regeneration, the hexagonal strontium ferrite powder preferably contains iron atoms, strontium atoms, oxygen atoms and rare earth atoms, and the content of atoms other than these atoms is 10.0 atomic % or less relative to 100 atomic % of iron atoms, more preferably in the range of 0 to 5.0 atomic %, and can also be 0 atomic %. That is, in one embodiment, the hexagonal strontium ferrite powder may not contain atoms other than iron atoms, strontium atoms, oxygen atoms and rare earth atoms. The content represented by the above atomic % is obtained by converting the content (unit: mass %) of each atom obtained by completely dissolving the hexagonal strontium ferrite powder into a value represented by atomic %. In addition, in the present invention and this specification, for a certain atom, "not containing" means that the content is completely dissolved and measured by an ICP analysis device, and the content is 0 mass %. The detection limit of the ICP analysis device is usually less than 0.01ppm (parts per million (fraction)) based on the mass standard. The above-mentioned “does not contain” is used to mean that the powder is contained in an amount less than the detection limit of an ICP analyzer. In one embodiment, the hexagonal strontium ferrite powder may not contain bismuth atoms (Bi).
[0158] Metal powder
[0159] Preferred specific examples of ferromagnetic powders include ferromagnetic metal powders. For details of ferromagnetic metal powders, for example, reference may be made to paragraphs 0137 to 0141 of Japanese Patent Application Laid-Open No. 2011-216149 and paragraphs 0009 to 0023 of Japanese Patent Application Laid-Open No. 2005-251351.
[0160] ε-Iron Oxide Powder
[0161] As a preferred specific example of a ferromagnetic powder, ε-iron oxide powder can also be cited. In the present invention and this specification, "ε-iron oxide powder" refers to a ferromagnetic powder in which the crystal structure of ε-iron oxide is detected as the main phase by X-ray diffraction analysis. For example, when the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by X-ray diffraction analysis belongs to the crystal structure of ε-iron oxide, it is judged that the crystal structure of ε-iron oxide is detected as the main phase. As a method for producing ε-iron oxide powder, a method of making it from goethite, a reverse micelle method, etc. are known. The above-mentioned production methods are all well known. In addition, regarding the method for producing ε-iron oxide powder in which a part of Fe is substituted by substitution atoms such as Ga, Co, Ti, Al, Rh, etc., reference can be made to J.Jpn.Soc.Powder Metallurgy Vol.61Supplement, No S1, pp S280-S284, JMater.Chem.C, 2013, 1, pp.5200-5206, etc. However, the method for producing the ε-iron oxide powder that can be used as the ferromagnetic powder in the magnetic layer of the magnetic recording medium is not limited to the method exemplified here.
[0162] The activation volume of ε-iron oxide powder is preferably between 300 and 1500 nm. 3 The micronized ε-iron oxide powder showing the above-mentioned activation volume is suitable for preparing a magnetic recording medium having excellent electromagnetic conversion characteristics. The activation volume of the ε-iron oxide powder is preferably 300 nm. 3 For example, it can be 500 nm. 3 Furthermore, from the viewpoint of further improving the electromagnetic conversion characteristics, the activation volume of the ε-iron oxide powder is more preferably 1400 nm. 3 Below, more preferably 1300nm 3 Below, more preferably 1200nm 3 Below, more preferably 1100nm 3 the following.
[0163] As an index for reducing thermal fluctuation (in other words, improving thermal stability), the anisotropy constant Ku can be cited. The ε-iron oxide powder may preferably have a value of 3.0×10 4 J / m 3 More preferably, the Ku may be 8.0×10 4 J / m 3 The Ku of the ε-iron oxide powder can be, for example, 3.0×105 J / m 3 However, a higher Ku indicates higher thermal stability and is preferred, and therefore, it is not limited to the values exemplified above.
[0164] From the viewpoint of improving the reproduction output when reproducing data recorded in the magnetic recording medium, it is preferred that the mass magnetization σs of the ferromagnetic powder contained in the magnetic recording medium is high. In this regard, in one embodiment, the σs of the ε-iron oxide powder may be 8 A·m 2 / kg or more, and can also be 12A·m 2 On the other hand, from the viewpoint of noise reduction, the σs of the ε-iron oxide powder is preferably 40 A·m 2 / kg or less, more preferably 35A·m 2 / kg or less.
[0165] In the present invention and this specification, unless otherwise specified, the average particle size of various powders such as ferromagnetic powder is a value measured by the following method using a transmission electron microscope.
[0166] The powder is photographed at a magnification of 100,000 times using a transmission electron microscope, and the total magnification is 500,000 times, and the powder is printed on photographic paper or displayed on a display to obtain a photograph of the particles constituting the powder. The target particle is selected from the obtained particle photograph, and the particle outline is traced with a digitizer to measure the size of the particle (primary particle). Primary particles refer to independent particles that are not agglomerated.
[0167] The above measurement is performed on 500 particles randomly extracted. The arithmetic mean of the particle size of the 500 particles thus obtained is taken as the average particle size of the powder. As the above-mentioned transmission electron microscope, for example, the transmission electron microscope H-9000 manufactured by Hitachi can be used. In addition, the measurement of the particle size can be performed using known image analysis software, for example, image analysis software KS-400 manufactured by Carl Zeiss. Unless otherwise specified, the average particle size shown in the embodiment described later is a value measured using the transmission electron microscope H-9000 manufactured by Hitachi as a transmission electron microscope and the image analysis software KS-400 manufactured by Carl Zeiss as an image analysis software. In the present invention and this specification, powder refers to a collection of multiple particles. For example, ferromagnetic powder refers to a collection of multiple ferromagnetic particles. In addition, the collection of multiple particles is not limited to a method in which the particles constituting the collection are in direct contact, but also includes a method in which the binder, additive, etc. described later are between the particles. The term particle is sometimes also used to represent powder.
[0168] As a method for collecting a sample powder from a magnetic recording medium for particle size measurement, for example, the method described in paragraph 0015 of Japanese Patent Application Laid-Open No. 2011-048878 can be adopted.
[0169] In the present invention and this specification, unless otherwise specified, the size of the particles constituting the powder (particle size) is the shape of the particles observed in the above-mentioned particle photograph.
[0170] (1) In the case of a needle-like, spindle-like, columnar shape (where the height is greater than the maximum long diameter of the base), etc., the length of the long axis constituting the particle, i.e., the long axis length, is used.
[0171] (2) In the case of a plate or column (where the thickness or height is smaller than the maximum major diameter of the plate surface or bottom surface), the maximum major diameter of the plate surface or bottom surface shall be used.
[0172] (3) When the major axis of the particle cannot be determined from the shape of a sphere, polyhedron, or indeterminate shape, the particle is expressed as a circle equivalent diameter. The circle equivalent diameter is a diameter obtained by a circular projection method.
[0173] The average needle ratio of the powder refers to the arithmetic average of the values obtained by measuring the length of the short axis of the particle, i.e., the short axis length, in the above measurement, and finding the value of (long axis length / short axis length) for each particle for the above 500 particles. Here, unless otherwise specified, the short axis length, in the case of (1) in the above definition of particle size, refers to the length of the short axis constituting the particle, and similarly, in the case of (2), refers to the thickness or height, respectively.
[0174] In the case of (3), since the major axis and the minor axis are indistinguishable, (major axis length / minor axis length) is regarded as 1 for the sake of convenience.
[0175] Furthermore, unless otherwise specified, when the shape of the particles is determined, for example, in the case of the above-mentioned definition of particle size (1), the average particle size is the average major axis length, and in the case of the definition of particle size (2), the average particle size is the average plate diameter. In the case of the definition of particle size (3), the average particle size is the average diameter (also referred to as the average particle size).
[0176] The content (filling rate) of the ferromagnetic powder in the magnetic layer is preferably in the range of 50 to 90 mass %, more preferably in the range of 60 to 90 mass % relative to the total mass of the magnetic layer. From the viewpoint of improving recording density, the filling rate of the ferromagnetic powder in the magnetic layer is preferably high.
[0177] (Non-magnetic powder)
[0178] The magnetic recording medium may include one or more non-magnetic powders in the magnetic layer. The non-magnetic powder preferably includes at least a non-magnetic powder that helps to form protrusions on the surface of the magnetic layer (hereinafter, referred to as a "protrusion forming agent"). In addition, the magnetic layer also preferably includes a non-magnetic powder that can function as an abrasive (hereinafter, referred to as an "abrasive") as the non-magnetic powder. The protrusion forming agent and the abrasive are further described below.
[0179] -Protrusion forming agent-
[0180] The protrusion forming agent can be an inorganic powder or an organic powder. For example, as an inorganic powder, inorganic oxides such as metal oxides, metal carbonates, metal sulfates, metal nitrides, metal carbides, metal sulfides and the like can be cited, preferably powders of inorganic oxides. The average particle size of the protrusion forming agent is preferably in the range of 90 to 200 nm, and more preferably in the range of 100 to 150 nm. In one embodiment, from the viewpoint of uniformity of friction characteristics, the particle size distribution of the protrusion forming agent is preferably a monodispersion showing a single peak, rather than a polydispersion having multiple peaks in the particle size distribution. From the viewpoint of the availability of monodisperse particles, the protrusion forming agent is preferably an inorganic powder, more preferably a colloidal particle. The "colloidal particles" in the present invention and this specification refer to particles that are dispersed without precipitation and can provide a colloidal dispersion when 1 g is added to 100 mL of the organic solvent, such as methyl ethyl ketone, cyclohexanone, toluene or ethyl acetate, or a mixed solvent containing two or more of the above solvents in any mixing ratio. The non-magnetic powder contained in the magnetic layer is a colloidal particle. If the non-magnetic powder used in forming the magnetic layer can be obtained, it is sufficient to evaluate whether the non-magnetic powder has properties that meet the definition of the above-mentioned colloidal particles. Alternatively, it is also possible to evaluate whether the non-magnetic powder taken out from the magnetic layer has properties that meet the definition of the above-mentioned colloidal particles.
[0181] Specific examples of colloidal particles include inorganic oxide colloidal particles such as SiO2, Al2O3, TiO2, ZrO2, and Fe2O3. Other examples include SiO2·Al2O3, SiO2·B2O3, TiO2·CeO2, SnO2·Sb2O3, SiO2·Al 2O3·Colloidal particles of composite inorganic oxides such as TiO2, TiO2·CeO2·SiO2. In addition, regarding the mark of composite inorganic oxides, "·" is used to indicate the composite inorganic oxide of the inorganic oxides recorded before and after it. For example, SiO2·Al2O3 refers to a composite inorganic oxide of SiO2 and Al2O3. As colloidal particles, colloidal particles of silicon dioxide (silica), i.e., colloidal silica particles (also referred to as "colloidal silica") are particularly preferred. In addition, regarding colloidal particles, reference can also be made to the records in paragraphs 0048 to 0049 of Japanese Patent Gazette No. 2017-68884.
[0182] The content of the protrusion forming agent of the magnetic layer is preferably 0.1 to 10.0 parts by mass, more preferably 0.1 to 5.0 parts by mass, and further preferably 1.0 to 5.0 parts by mass relative to 100.0 parts by mass of the ferromagnetic powder. In the present invention and this specification, a certain component can be used in one kind or in two or more kinds. When using two or more kinds, the content refers to the total content of the two or more kinds.
[0183] (Abrasive)
[0184] The abrasive is a component that can exert the ability to remove attachments attached to the magnetic head during operation (abrasiveness). Examples of the abrasive include aluminum oxide (Al2O3), silicon carbide, boron carbonate (B4C), TiC, chromium oxide (Cr2O3), cerium oxide, zirconium oxide (ZrO2), iron oxide, diamond and other powders that are commonly used as abrasives for magnetic layers. Among them, aluminum oxide such as α-alumina, silicon carbide and diamond powders are preferred. The abrasive content of the magnetic layer is preferably 1.0 to 20.0 parts by mass, more preferably 3.0 to 15.0 parts by mass, and further preferably 4.0 to 10.0 parts by mass, relative to 100.0 parts by mass of the ferromagnetic powder. In addition, regarding the particle size of the abrasive, the specific surface area, which is an indicator of the particle size, can be, for example, 14 m 2 / g or more, preferably 16m 2 / g or more, more preferably 18m 2 / g or more. In addition, the specific surface area of the abrasive can be, for example, 40 m 2 / g or less.
[0185] (Binder, curing agent)
[0186] The magnetic recording medium can contain a binder in the magnetic layer. As the binder of the magnetic layer, various resins commonly used as binders for coated magnetic recording media can be used. For example, as the binder of the magnetic layer, a resin selected from polyurethane resin, polyester resin, polyamide resin, vinyl chloride resin, styrene, acrylonitrile, acrylic resin copolymerized with methyl methacrylate, cellulose resin such as nitrocellulose, epoxy resin, phenoxy resin, polyvinyl acetal, polyvinyl butyral, etc. can be used alone or in combination with multiple resins. Among these, polyurethane resin, acrylic resin, cellulose resin and vinyl chloride resin are preferred. For the above binders, reference can be made to paragraphs 0028 to 0031 of Japanese Patent Publication No. 2010-24113. The average molecular weight of the resin used as the binder of the magnetic layer can be, for example, 10,000 or more and 200,000 or less as a weight average molecular weight. The content of the binder of the magnetic layer can be, for example, 1.0 to 30.0 parts by mass relative to 100.0 parts by mass of the ferromagnetic powder.
[0187] In addition, a curing agent can also be used together with the resin that can be used as a binder. In one embodiment, the curing agent can be a compound that undergoes a curing reaction (crosslinking reaction) by heating, that is, a thermosetting compound, and in another embodiment, it can be a photocurable compound that undergoes a curing reaction (crosslinking reaction) by light irradiation. By performing a curing reaction in the magnetic layer formation process, at least a portion of the curing agent can be contained in the magnetic layer in a state of reacting (crosslinking) with other components such as a binder. This is also the same for a layer formed using the composition when the composition for forming other layers contains a curing agent. A preferred curing agent is a thermosetting compound, preferably a polyisocyanate. For details of polyisocyanates, reference can be made to paragraphs 0124 to 0125 of Japanese Patent Publication No. 2011-216149. Regarding the curing agent, for example, it can be used in an amount of 0 to 80.0 parts by mass of the composition relative to 100.0 parts by mass of the binder, and from the viewpoint of improving the strength of the magnetic layer, it is preferably used in an amount of 50.0 to 80.0 parts by mass.
[0188] (additive)
[0189] The magnetic layer may further include one or more additives as needed. As an additive, for example, the above-mentioned curing agent can be cited. In addition, as additives contained in the magnetic layer, lubricants, dispersants, dispersing aids, mildew inhibitors, antistatic agents, antioxidants, etc. can be cited. The additive can be appropriately selected from commercial products or manufactured using a known method according to the desired properties, and used in any amount. For example, regarding lubricants, reference can be made to paragraphs 0030 to 0033, 0035, and 0036 of Japanese Patent Publication No. 2016-126817. Lubricants may also be included in the non-magnetic layer described later. Regarding lubricants that can be included in the non-magnetic layer, reference can be made to paragraphs 0030 to 0031, 0034, 0035, and 0036 of Japanese Patent Publication No. 2016-126817. Regarding dispersants, reference can be made to paragraphs 0061 and 0071 of Japanese Patent Publication No. 2012-133837. A dispersant may also be added to the composition for forming a non-magnetic layer. For dispersants that can be added to the composition for forming a non-magnetic layer, reference may be made to paragraph 0061 of Japanese Patent Application Publication No. 2012-133837. As an example of an additive that can be used to improve the dispersibility of the abrasive for a magnetic layer containing an abrasive, the dispersants described in paragraphs 0012 to 0022 of Japanese Patent Application Publication No. 2013-131285 may be cited.
[0190] <Non-magnetic support>
[0191] Next, non-magnetic support (hereinafter, also simply recorded as "support".) is described. As non-magnetic support, known non-magnetic supports such as polyethylene terephthalate, polyethylene naphthalate, polyamide, polyamide-imide, aromatic polyamide, etc. that have been biaxially stretched can be enumerated. Among these, preferred polyethylene terephthalate, polyethylene naphthalate and polyamide. These supports can be subjected to corona discharge, plasma treatment, easy bonding treatment, heat treatment, etc. in advance.
[0192] <Back coating>
[0193] The above-mentioned magnetic recording medium can also have a back coating layer containing non-magnetic powder on the surface side opposite to the surface side with magnetic layer and non-magnetic layer of the non-magnetic support. Alternatively, the above-mentioned magnetic recording medium can also be a magnetic recording medium without a back coating layer. The back coating layer preferably contains either or both of carbon black and inorganic powder. Regarding the details of the back coating layer, the known technology related to the back coating layer can be applied. And the back coating layer can include a binder. Regarding the binder included in the back coating layer and the various additives that can be arbitrarily included, the previous records and known technologies related to the formulation of the magnetic layer and / or non-magnetic layer can be arbitrarily applied. For example, regarding the back coating layer, it is possible to refer to the 0018 to 0020 paragraphs of the Japanese Patent Publication No. 2006-331625 and the records of the 4th column, the 65th line to the 5th column, the 38th line of the U.S. Patent No. 7,029,774 specification.
[0194] <Manufacturing process>
[0195] (Preparation of Compositions for Forming Each Layer)
[0196] The composition for forming the magnetic layer, the non-magnetic layer or the back coating layer comprises the various components described above, and generally comprises a solvent. As a solvent, one or more of the various solvents commonly used in the manufacture of the coated magnetic recording medium can be used. The solvent content of the composition for forming each layer is not particularly limited. Regarding the solvent, reference can be made to paragraph 0153 of Japanese Patent Publication No. 2011-216149. The solid content concentration and solvent composition of the composition for forming each layer can be appropriately adjusted as long as they correspond to the operational adaptability of the composition, the coating conditions and the thickness of each layer to be formed. The process for preparing the composition for forming the magnetic layer, the non-magnetic layer or the back coating layer generally includes at least a kneading process, a dispersion process and a mixing process provided before and after these processes as required. Each process can be divided into two or more stages. Regarding the centrifugal separation treatment of the dispersion of the protrusion forming agent, as described above. All raw materials used in the preparation of the composition for forming each layer can be added at the beginning or midway of any process. In addition, each raw material can be added separately in two or more processes. For example, the binder can be separately put into the kneading process, the dispersion process, and the mixing process for adjusting the viscosity after dispersion. In the manufacturing process of the above-mentioned magnetic recording medium, existing known manufacturing technology can be used as a part of the process. In the mixing process, it is preferred to use an open kneader, a continuous kneader, a pressurized kneader, an extruder and other devices with strong mixing power. The details of the mixing process are recorded in Japanese Patent Laid-Open No. 1-106338 Gazette and Japanese Patent Laid-Open No. 1-79274 Gazette. As a disperser, various known dispersers using shear force such as a bead mill, a ball mill, a sand mill or a homogenizer can be used. Dispersion beads can be preferably used in the dispersion. As dispersion beads, ceramic beads, glass beads, etc. can be cited, preferably zirconium dioxide beads. Two or more beads can also be used in combination. The bead diameter (particle size) and bead filling rate of the dispersion beads are not particularly limited, and can be set according to the powder of the dispersion object. It is also possible to filter the composition for forming each layer by a known method before implementing the coating process. Filtration can be performed by filtering, for example, through a filter. As the filter used for filtration, for example, a filter having a pore size of 0.01 to 3 μm (for example, a glass fiber filter, a polypropylene filter, etc.) can be used.
[0197] (Coating process)
[0198] The non-magnetic layer and the magnetic layer can be formed by applying the non-magnetic layer forming composition and the magnetic layer forming composition successively or simultaneously. The back coating layer can be formed by applying the back coating layer forming composition to the surface opposite to the surface of the non-magnetic support body with the non-magnetic layer and the magnetic layer (or the non-magnetic layer and / or the magnetic layer are additionally provided). For details of the coating for forming each layer, reference can be made to paragraph 0066 of Japanese Patent Publication No. 2010-231843.
[0199] (Other processes)
[0200] For various other processes for manufacturing magnetic recording media, for example, reference can be made to paragraphs 0067 to 0070 of Japanese Patent Publication No. 2010-231843. For example, regarding the orientation treatment, the coating layer of the magnetic layer forming composition can be oriented in the orientation zone while the coating layer is in a wet state. Regarding the orientation treatment, various known techniques headed by the description of paragraph 0052 of Japanese Patent Publication No. 2010-24113 can be applied. For example, the vertical orientation treatment can be carried out by a known method such as a method of using oppositely polarized magnets. In the orientation zone, the drying speed of the coating layer can be controlled according to the temperature, air volume and / or conveying speed of the drying wind in the orientation zone. In addition, the coating layer can be pre-dried before being conveyed to the orientation zone. As an example, the magnetic field intensity in the vertical orientation treatment can be set to 0.10 to 0.80T, or it can also be set to 0.10 to 0.60T. In addition, as a treatment for improving the surface smoothness of the magnetic recording medium, a calendering treatment can be performed. Regarding the conditions for the calendering treatment, for example, the calendering pressure (linear pressure) may be 200 to 500 kN / m, preferably 250 to 350 kN / m. The calendering temperature (surface temperature of the calendering roll) may be, for example, 70 to 120° C., preferably 80 to 100° C., and the calendering speed may be, for example, 50 to 300 m / min, preferably 50 to 200 m / min.
[0201] The magnetic recording medium involved in one embodiment of the present invention can be a belt-shaped magnetic recording medium (tape) or a disk-shaped magnetic recording medium (disk). For example, the magnetic tape is usually contained in a tape cassette, and the tape cassette is installed in a magnetic recording and reproducing device. In order to enable the magnetic recording medium to perform head tracking in the magnetic recording and reproducing device, a servo pattern can also be formed by a known method. "Formation of a servo pattern" can also be said to be "recording of a servo signal." Below, the formation of a servo pattern is explained using a magnetic tape as an example.
[0202] The servo pattern is usually formed along the longitudinal direction of the magnetic tape. As a control method using a servo signal (servo control), there are timing-based servo (TBS), amplitude servo, frequency servo, and the like.
[0203] As shown in ECMA (European Computer Manufacturers Association)-319 (June 2001), a timing-based servo method is adopted in a magnetic tape that complies with the LTO (Linear Tape-Open) specification (generally referred to as "LTO tape".). In this timing-based servo method, a servo pattern is formed by continuously arranging a plurality of non-parallel magnetic stripes (also referred to as "servo stripes") along the length direction of the magnetic tape. As described above, the reason why the servo pattern is composed of a pair of non-parallel magnetic stripes is to inform the servo signal reading element passing over the servo pattern of the passing position. Specifically, the pair of magnetic stripes are formed in such a way that the interval between them continuously changes along the width direction of the magnetic tape, and by reading the interval by the servo signal reading element, the relative position of the servo pattern and the servo signal reading element can be known. The information of the relative position enables tracking of the data track. Therefore, a plurality of servo tracks are usually set along the width direction of the magnetic tape on the servo pattern.
[0204] The servo band is composed of servo signals that are continuous in the length direction of the tape. There are usually multiple servo bands on the tape. For example, in an LTO tape, there are five servo bands. The area between two adjacent servo bands is called a data band. The data band is composed of multiple data tracks, each of which corresponds to a servo track.
[0205] Furthermore, in one method, as shown in Japanese Patent Application Laid-Open No. 2004-318983, information indicating the number of the servo band (also referred to as "servo band ID (identification)" or "UDIM (Unique Data Band Identification Method) information") is embedded in each servo band. The servo band ID is recorded by shifting a specific servo band in a pair of servo bands that exist in plurality in the servo band so that its position is relatively displaced in the longitudinal direction of the magnetic tape. Specifically, the shifting method of the specific servo band in a pair of servo bands that exist in plurality is changed for each servo band. Thus, the recorded servo band ID is unique for each servo band, and thus, by only reading one servo band with the servo signal reading element, the servo band can be uniquely identified.
[0206] Another method of uniquely identifying a servo band is a method using an interleaving method as disclosed in ECMA-319 (June 2001). In this interleaving method, a set of a plurality of pairs of magnetic stripes (servo stripes) that are continuously arranged in the length direction of the magnetic tape and are not parallel to each other is recorded in such a manner that each servo stripe is staggered along the length direction of the magnetic tape. The combination of the staggering method between adjacent servo stripes is unique in the entire magnetic tape, so that when the servo pattern is read by two servo signal reading elements, the servo band can also be uniquely identified.
[0207] Furthermore, as shown in ECMA-319 (June 2001), information indicating the position in the longitudinal direction of the tape (also referred to as "LPOS (Longitudinal Position) information") is usually embedded in each servo band. Similar to the UDIM information, the LPOS information is recorded by shifting the position of a pair of servo bands in the longitudinal direction of the tape. However, unlike the UDIM information, the LPOS information has the same signal recorded in each servo band.
[0208] Other information different from the UDIM information and LPOS information can also be embedded in the servo band. In this case, the embedded information may be different for each servo band like the UDIM information, or may be common to all servo bands like the LPOS information.
[0209] Furthermore, as a method of embedding information in the servo band, methods other than the above can be adopted. For example, a predetermined pair may be removed from a pair of servo stripes to record a predetermined code.
[0210] The magnetic head used to form the servo pattern is called a servo write head. The servo write head has a pair of gaps corresponding to the above-mentioned pair of magnetic stripes, which is the number of servo bands. Usually, a core and a coil are connected to each pair of gaps, and by supplying a current pulse to the coil, the magnetic field generated in the core can generate a leakage magnetic field in the pair of gaps. When forming a servo pattern, by inputting a current pulse while allowing the magnetic tape to travel on the servo write head, the magnetic pattern corresponding to the pair of gaps can be transferred to the magnetic tape to form a servo pattern. The width of each gap can be appropriately set according to the density of the servo pattern to be formed. The width of each gap can be set, for example, to less than 1 μm, 1 to 10 μm, or more than 10 μm.
[0211] Before forming a servo pattern on the magnetic tape, the magnetic tape is usually subjected to a demagnetization (demagnetization) process. The demagnetization process can be performed by applying the same magnetic field to the magnetic tape using a DC magnet or an AC magnet. There are two types of demagnetization processes: DC (Direct Current) demagnetization and AC (Alternating Current) demagnetization. AΛ demagnetization is performed by gradually reducing the intensity of the magnetic field applied to the magnetic tape while reversing the direction of the magnetic field. On the other hand, DΛ demagnetization is performed by applying a magnetic field in one direction to the magnetic tape. There are two further methods of DΛ demagnetization. The first method is horizontal DΛ demagnetization in which a magnetic field in one direction is applied along the length direction of the magnetic tape. The second method is vertical DΛ demagnetization in which a magnetic field in one direction is applied along the thickness direction of the magnetic tape. The demagnetization process can be performed on the entire magnetic tape or on each servo band of the magnetic tape.
[0212] The orientation of the magnetic field of the formed servo pattern is determined according to the orientation of the demagnetization. For example, when horizontal DΛ demagnetization is applied to the magnetic tape, the servo pattern is formed in a manner in which the orientation of the magnetic field is opposite to the orientation of the demagnetization. As a result, the output of the servo signal obtained by reading the servo pattern can be increased. In addition, as shown in Japanese Patent Gazette No. 2012-53940, when a magnetic pattern is transferred using the above-mentioned gap to a magnetic tape that has been vertically DΛ erased, the servo signal obtained by reading the formed servo pattern is in the shape of a unipolar pulse. On the other hand, when a magnetic pattern is transferred using the above-mentioned gap to a magnetic tape that has been horizontally DΛ demagnetized, the servo signal obtained by reading the formed servo pattern is in the shape of a bipolar pulse.
[0213] The magnetic tape is usually stored in a tape cassette, and the tape cassette is mounted in a magnetic recording and reproducing device.
[0214] [Cassette]
[0215] One aspect of the present invention relates to a magnetic tape cassette including the above-mentioned tape-shaped magnetic recording medium (ie, magnetic tape).
[0216] The details of the magnetic tape contained in the above-mentioned magnetic tape cassette are as described above.
[0217] In a tape cassette, the tape is generally contained inside the cassette body in a state where the tape is wound onto a reel. The reel is rotatably provided inside the cassette body. As a tape cassette, a single-reel type tape cassette having one reel inside the cassette body and a double-reel type tape cassette having two reels inside the cassette body are widely used. If the single-reel type tape cassette is installed in a magnetic recording and reproducing device in order to record and / or reproduce the data of the tape, the tape is pulled out from the tape cassette and wound onto the reel on the side of the magnetic recording and reproducing device. A magnetic head is arranged on the tape conveying path from the tape cassette to the winding reel. The tape is fed out and wound between the reel (supply reel) on the side of the tape cassette and the reel (winding reel) on the side of the magnetic recording and reproducing device. During this period, the magnetic head contacts and slides with the surface of the magnetic layer side of the tape, thereby recording and / or reproducing the data. In contrast, the supply reel and the winding reel of the double-reel type tape cassette are provided inside the tape cassette. The magnetic tape cassette may be a single-reel type or a double-reel type. The magnetic tape cassette may include the magnetic tape according to one aspect of the present invention, and other aspects may use known techniques.
[0218] [Magnetic recording and reproducing device]
[0219] One aspect of the present invention relates to a magnetic recording and reproducing device including the above-mentioned magnetic recording medium.
[0220] In the present invention and this specification, a "magnetic recording and reproducing device" refers to a device that can perform at least one of recording data on a magnetic recording medium and reproducing data recorded on the magnetic recording medium. This device is generally called a drive. The above-mentioned magnetic recording and reproducing device can be, for example, a sliding-type magnetic recording and reproducing device. A sliding-type magnetic recording and reproducing device refers to a device in which the surface of the magnetic layer side contacts and slides with the magnetic head when recording data on a magnetic recording medium and / or reproducing the recorded data. For example, the above-mentioned magnetic recording and reproducing device can include the above-mentioned tape cassette in a detachable manner.
[0221] The magnetic recording and reproducing device may include a magnetic head. The magnetic head may be a recording head capable of recording data on a magnetic recording medium, or a reproducing head capable of reproducing data recorded in a magnetic recording medium. Furthermore, in one embodiment, the magnetic recording and reproducing device may include both a recording head and a reproducing head in the form of independent magnetic heads. In another embodiment, the magnetic head included in the magnetic recording and reproducing device may also be a structure in which one magnetic head includes both an element for recording data (recording element) and an element for reproducing data (reproducing element). Hereinafter, the element for recording data and the element for reproducing data are collectively referred to as "data elements". As a reproducing head, it is preferred to include a magnetic head (MR head) that includes a magnetoresistive (MR) element as a reproducing element that can read data recorded on a magnetic recording medium with good sensitivity. As the MR head, various well-known MR heads such as AMR (Anisotropic Magnetoresistive) head, GMR (Giant Magnetoresistive) head, TMR (Tunnel Magnetoresistive) head, etc. can be used. In addition, the head for recording data and / or reproducing data can include a servo signal reading element. Alternatively, a head (servo head) having a servo signal reading element can be included in the above-mentioned magnetic recording and reproducing device as a head different from the head for recording data and / or reproducing data. For example, a head for recording data and / or reproducing recorded data (hereinafter, also referred to as a "recording and reproducing head") can include two servo signal reading elements, and the two servo signal reading elements can respectively read two adjacent servo bands at the same time. One or more data elements can be configured between the two servo signal reading elements.
[0222] In the magnetic recording and reproducing device, the recording of data on the magnetic recording medium and / or the regeneration of data recorded in the magnetic recording medium can be performed by making the surface of the magnetic layer side of the magnetic recording medium contact and slide with the magnetic head. The magnetic recording and reproducing device includes the magnetic recording medium involved in one embodiment of the present invention, and known technologies can be applied to other parts.
[0223] For example, when recording data and / or reproducing recorded data, first, tracking using a servo signal is performed. That is, by making the servo signal reading element follow a predetermined servo track, the data element can be controlled to pass over a target data track. The movement of the data track is performed by changing the servo track read by the servo signal reading element in the tape width direction.
[0224] Furthermore, the recording and reproducing magnetic head can also record and / or reproduce other data bands. At this time, the servo signal reading element is moved to a predetermined servo band using the UDIM information described above, and tracking of the servo band is started.
[0225] Example
[0226] Hereinafter, the present invention will be described based on examples. However, the present invention is not limited to the embodiments shown in the examples. The "parts" and "%" described below are based on mass. In addition, unless otherwise specified, the processes and evaluations described below are performed in an environment with an atmospheric temperature of 23°C ± 1°C.
[0227] In Examples and Comparative Examples, the polyurethane resin A used for preparing the non-magnetic layer-forming composition is a polyurethane resin having an aromatic ring structure synthesized by the following method.
[0228] [Synthesis of polyurethane resin A having an aromatic ring structure]
[0229] The polyester polyol (a) shown in Table 2, and the EO (ethylene oxide) adduct of HPN (2,2-dimethyl-1,3-propanediol mono(hydroxypivalate)) as a short-chain diol and sodium sulfoisophthalate, that is, compound (b), were dissolved in a 30% solution of cyclohexanone at a liquid temperature of 60°C in a nitrogen stream in a container equipped with a reflux cooler and a stirrer and purged with nitrogen in advance. Next, 60 ppm (mass basis) of dibutyltin dilaurate was added as a catalyst and further dissolved for 15 minutes. Furthermore, MDI (4,4'-diphenylmethane diisocyanate) was added as a diisocyanate, and a heating reaction was carried out at a liquid temperature of 90°C for 6 hours to obtain a polyurethane resin A. The raw material composition ratio was set to the value shown in Table 1.
[0230] [Table 1]
[0231]
[0232] Note) Based on the amount of polyester polyol (a) (100% by mass).
[0233] [Chemical formula 1]
[0234] HPN (2,2-dimethyl-1,3-propanediol mono(hydroxypivalate))
[0235]
[0236] [Chemical formula 2]
[0237] Compound (b)
[0238]
[0239] [Chemical formula 3]
[0240] MDI (4,4'-diphenylmethane diisocyanate)
[0241]
[0242] [Table 2]
[0243]
[0244] Note: Based on the amount of NPG (100 mol %).
[0245] The number average molecular weight of the polyester polyol (a) shown in Table 2 is a value calculated from the hydroxyl value measured by the method described in JIS Standard K1557-1:2007.
[0246] [Chemical formula 4]
[0247] NPG (neopentyl glycol) (other name: 2,2-dimethyl-1,3-propanediol)
[0248]
[0249] The weight average molecular weight of the polyurethane resin A determined by the method described above was 67,000.
[0250] For polyurethane resin A, the content of sulfonic acid metal base (SO3Na) was calculated by the following formula based on the metal component Na concentration, and the result was 70eq / ton. In the following formula, "23" is the atomic weight of Na. The Na concentration (unit: ppm (mass basis)) was calculated by carbonizing 0.1 g of the sample and dissolving it in an acid, and then analyzing it by atomic absorption.
[0251] Sulfonic acid metal alkali (SO3Na) content (eq / ton) = Na concentration (ppm) / 23
[0252] Polyurethane resin A was analyzed in chloroform-d solvent using a nuclear magnetic resonance analyzer (NMR) GEMINI-200 manufactured by Varian Medical Systems, Inc. 1 H-NMR analysis was used to determine the polyurethane composition based on its integral ratio. 1 The urethane group concentration was determined by the following formula using the mol% of isocyanate determined by H-NMR analysis. The determined urethane group concentration was 3.5 meq / g.
[0253] Carbamate group concentration (meq / g) = 10 3×{2×mol% of isocyanate×(1 / 100)} / unit molecular weight of polyurethane)
[0254] [Example 1]
[0255] <Formula for magnetic layer forming composition>
[0256] (Magnetic fluid)
[0257] Hexagonal barium ferrite powder: 100.0 parts
[0258] (Average particle size: 17nm, activation volume: 1300nm 3 )
[0259] Oleic acid: 1.5 parts
[0260] Vinyl chloride resin: 10.0 parts
[0261] (MR-104 manufactured by KANEKA CORPORATION)
[0262] Polyurethane resin: 4.0 parts
[0263] (UR-4800 (polyester polyurethane resin containing sulfonic acid group) manufactured by TOYOBO Co., Ltd.)
[0264] Methyl ethyl ketone: 300.0 parts
[0265] Cyclohexanone: 300.0 parts
[0266] (Abrasive Liquid)
[0267] Alumina powder (specific surface area 19m 2 / g of α-alumina): 9.0 parts
[0268] Vinyl chloride resin: 0.7 parts
[0269] (MR-110 manufactured by KANEKA CORPORATION)
[0270] Cyclohexanone: 20.0 parts
[0271] (Protrusion forming agent liquid)
[0272] Colloidal silica particles (colloidal silica) (average particle size: 150 nm): 2.0 parts
[0273] Methyl ethyl ketone: 8.0 parts
[0274] (Other ingredients)
[0275] Stearic acid: 1.0 parts
[0276] Stearamide: 0.3 parts
[0277] Butyl stearate: 1.5 parts
[0278] Methyl ethyl ketone: 110.0 parts
[0279] Cyclohexanone: 110.0 parts
[0280] Polyisocyanate (CORONATE L manufactured by TOSOH CORPORATION): 2.5 parts
[0281] <Formula for Nonmagnetic Layer Forming Composition>
[0282] Carbon black: refer to Table 3
[0283] (Specific surface area: refer to Table 3, pH: refer to Table 3)
[0284] Oleic acid: 4.0 parts
[0285] Polyurethane resin A: Refer to Table 3
[0286] Methyl ethyl ketone: 510.0 parts
[0287] Cyclohexanone: 200.0 parts
[0288] Stearic acid: 1.5 parts
[0289] Stearamide: 0.3 parts
[0290] Butyl stearate: 1.5 parts
[0291] <Formula for Back Coat Layer Forming Composition>
[0292] Carbon black: 100.0 parts
[0293] (Average particle size: 40nm, DBP (Dibutyl phthalate) oil absorption: 74cm 3 / 100g)
[0294] Copper phthalocyanine: 3.0 parts
[0295] Nitrocellulose: 25.0 parts
[0296] Polyurethane resin: 60.0 parts
[0297] (UR-8401 (polyester polyurethane resin containing sulfonic acid group) manufactured by TOYOBO CO., LTD.)
[0298] Polyester resin: 4.0 parts
[0299] (VYLON 500 manufactured by TOYOBO C0., LTD.)
[0300] Alumina powder (surface area 17m 2 / g of α-alumina): 1.0 part
[0301] Polyisocyanate: 15.0 parts
[0302] (CORONATE L manufactured by TOSOH CORPORATION)
[0303] Methyl ethyl ketone: 600.0 parts
[0304] Toluene: 600.0 parts
[0305] <Preparation of Compositions for Forming Each Layer>
[0306] A composition for forming a magnetic layer was prepared as follows.
[0307] After mixing and diluting the components of the magnetic liquid using an open kneader, a horizontal bead mill was used to disperse the components 30 times using zirconium oxide (ZrO2) beads with a particle size of 0.1 mm (hereinafter referred to as "Zr beads") at a bead filling rate of 80% by volume and a rotor tip peripheral speed of 10 m / s, wherein the residence time for each time was set to 2 minutes.
[0308] For the abrasive liquid, after preparing a mixture of the components of the abrasive liquid described above (alumina powder, vinyl chloride resin and cyclohexanone), the mixture was placed in a horizontal bead mill disperser together with Zr beads with a particle size of 0.3 mm, and the bead volume / (abrasive liquid volume+bead volume) was adjusted to 80 volume %, and the bead mill dispersion treatment was carried out for 120 minutes. The treated solution was taken out and subjected to ultrasonic dispersion filtration treatment using a flow-type ultrasonic dispersion filtration device.
[0309] The magnetic liquid, polishing agent liquid, protrusion forming agent liquid and other components were introduced into a dissolver stirrer, stirred at a peripheral speed of 10 m / s for 30 minutes, treated three times with a flow ultrasonic disperser at a flow rate of 7.5 kg / min, and filtered with a 1 μm filter to prepare a magnetic layer forming composition.
[0310] A nonmagnetic layer-forming composition was prepared as follows.
[0311] The above components except the lubricant (stearic acid, stearamide and butyl stearate) were mixed and diluted by an open kneader, and then dispersed by a horizontal bead mill. Then, the lubricant (stearic acid, stearamide and butyl stearate) and methyl ethyl ketone for coating thickness adjustment were added, and stirred and mixed by a dissolving stirrer to prepare a composition for forming a non-magnetic layer.
[0312] In Example 1, and Examples 2 to 8 described later, and Comparative Examples 1 to 3, when preparing the non-magnetic layer forming composition, methyl ethyl ketone for coating thickness adjustment was used in an amount ranging from 70.0 to 510.0 parts by mass relative to 100.0 parts by mass of the non-magnetic powder used to prepare the non-magnetic layer forming composition.
[0313] A back coat layer-forming composition was prepared as follows.
[0314] The above components except polyisocyanate were introduced into a dissolver stirrer, stirred at a peripheral speed of 10 m / s for 30 minutes, and then dispersed using a horizontal bead mill disperser. Then, polyisocyanate was added, and stirred and mixed using a dissolver stirrer to prepare a back coating layer forming composition.
[0315] <Tape Production>
[0316] On one surface of a biaxially stretched polyethylene naphthalate support having a thickness of 6.0 μm, a non-magnetic layer forming composition was applied and dried in such a manner that the thickness after drying became the thickness shown in Table 4, thereby forming a non-magnetic layer. On the formed non-magnetic layer, the magnetic layer forming composition prepared above was applied in such a manner that the thickness after drying became the thickness shown in Table 4 to form a coating layer. While the coating layer of the magnetic layer forming composition was in a wet (undried) state, a vertical orientation treatment was performed by applying a magnetic field with a magnetic field intensity of 0.15 T to the surface of the coating layer in a vertical direction. Then, the coating layer was dried to form a magnetic layer. Then, on the surface of the support opposite to the surface on which the non-magnetic layer and the magnetic layer were formed, a back coating layer forming composition was applied and dried in such a manner that the thickness after drying became 0.5 μm. Then, a calendering treatment was performed using a calendering treatment machine consisting only of metal rollers at a speed of 100 m / min, a linear pressure of 294 kN / m, and a calendering temperature of 100°C. Then, heat treatment was performed for 36 hours in an environment with an ambient temperature of 70° C. After the heat treatment, the tape was divided into pieces with a width of 1 / 2 inch (1 inch=0.0254 m) to obtain a magnetic tape.
[0317] [Example 2 to Example 8, Comparative Example 1 to Comparative Example 3]
[0318] The items shown in the table below were changed as shown in the table below, and except for this point, a magnetic tape was produced by the method described in Example 1. The thickness of the non-magnetic layer was adjusted according to the amount of methyl ethyl ketone used for coating thickness adjustment when preparing the composition for forming the non-magnetic layer. The thickness of the magnetic layer was adjusted according to the coating amount of the composition for forming the magnetic layer.
[0319] In the examples and comparative examples in which a vinyl chloride resin was used as a binder for the non-magnetic layer, MR-104 manufactured by KANEKA CORPORATION was used as the vinyl chloride resin.
[0320] Comparative Example 1 is a comparative example according to Example 1 of Japanese Patent Application Laid-Open No. 2020-144960 (Patent Document 1), and Comparative Example 3 is a comparative example according to Example 10 of Japanese Patent Application Laid-Open No. 2005-267714 (Patent Document 3).
[0321] [Evaluation method]
[0322] <Chlorine content (magnetic layer + non-magnetic layer), iron content (magnetic layer + non-magnetic layer)>
[0323] For each magnetic tape of the example and the comparative example, the chlorine content (magnetic layer + non-magnetic layer) and the iron content (magnetic layer + non-magnetic layer) were determined by the above-described method.
[0324] <Porosity and various thicknesses of non-magnetic layer>
[0325] A sample for cross-sectional observation was prepared by the method described above as a specific example. Using the prepared sample for cross-sectional observation, the porosity of the non-magnetic layer and the thickness of the magnetic layer were obtained by the method described above. The thickness of the non-magnetic layer was also obtained by the method described above as a method for measuring the thickness of the magnetic layer. As a field emission scanning electron microscope (FE-SEM) for SEM observation, FE-SEMS4800 manufactured by Hitachi, Ltd. was used.
[0326] <Magnetic Layer Bm>
[0327] For each magnetic tape in the embodiment and comparative example, a vibrating sample fluxmeter (manufactured by Toyo-Kogyo Co., Ltd.) was used to scan the external magnetic field of the magnetic tape and measure it at a measuring temperature of 23°C±1°C, under the conditions of a maximum external magnetic field of 15kOe and a scanning speed of 600e / sec, thereby calculating the magnetization amount Φm [G·μm].
[0328] The magnetic layer Bm is calculated as a value obtained by dividing Φm [(G·μm)] by the magnetic layer thickness (unit: μm) obtained above.
[0329] The magnetic layer Bm is preferably 1000G (Gauss) or more, and more preferably 1100G or more, 1200G or more, and 1300G or more. From the viewpoint of improving electromagnetic conversion characteristics, the higher the magnetic layer Bm, the more preferred. In one embodiment, the magnetic layer Bm can be, for example, 3000G or less, 2500G or less, or 2000G or less.
[0330] <Electromagnetic Conversion Characteristics (SNR: Signal-to-Noise ratio)>
[0331] For each magnetic tape of the embodiment and comparative example, the SNR was measured using a 1 / 2 inch reel tester with a magnetic head fixed thereon under an environment of a temperature of 23°C and a relative humidity of 50%. The head / tape relative speed was set to 6 m / sec. A MIG (Metal-In-Gap) head (gap length 0.15 μm, track width 1.0 μm, 1.8 T) was used for recording, and the recording current was set to the optimal recording current for each magnetic tape. As a reproducing head, a GMR head with an element thickness of 15 nm, a shield spacing of 0.1 μm, and a track width of 1.0 μm was used. A signal of a linear recording density (325 kfci) was recorded, and the regenerated signal was measured using a spectrum analyzer manufactured by Shibasoku Co., Ltd. The ratio of the output of the carrier signal to the integrated noise in the entire bandwidth of the spectrum was taken as the SNR, and was calculated as a relative value with respect to Comparative Example 1 as a reference (0.0 dB). The unit kfci is the unit of linear recording density (not convertible to the SI unit system). The signal uses the portion of the tape after it starts traveling where the signal is sufficiently stable.
[0332] <ΔSNR>
[0333] The magnetic tape after the evaluation of the electromagnetic conversion characteristics was stored in an environment of an ambient temperature of 60° C. and a relative humidity of 90% for 2 weeks, and then the SNR was measured by the above method. ΔSNR was calculated by the following formula.
[0334] ΔSNR = SNR measured after storage - SNR measured before storage
[0335] The above results are shown in the following table.
[0336]
[0337]
[0338] From the results shown in Table 4, it can be confirmed that in the magnetic tapes of Examples 1 to 8, the degradation of the electromagnetic conversion characteristics after storage under severe conditions is small.
[0339] Industrial Applicability
[0340] The present invention is useful in the technical field of various magnetic recording media such as magnetic tapes for data storage.
Claims
1. A magnetic recording medium comprising a non-magnetic support and a magnetic layer containing ferromagnetic powder, A non-magnetic layer containing non-magnetic powder is further provided between the non-magnetic support and the magnetic layer. The total chlorine content of the magnetic layer and the non-magnetic layer was 30.0 mg / m 2 The following, and The total iron content of the magnetic layer and the non-magnetic layer was 300.0 mg / m 2 the following.
2. The magnetic recording medium according to claim 1, wherein In a cross-sectional image obtained by photographing with a scanning electron microscope, the porosity of the nonmagnetic layer is 10.0% or less.
3. The magnetic recording medium according to claim 1, wherein The non-magnetic powder of the non-magnetic layer includes carbon black.
4. The magnetic recording medium according to claim 3, wherein: The non-magnetic layer contains 50.0 mass % or more of carbon black based on the total amount of the non-magnetic powder.
5. The magnetic recording medium according to claim 1, wherein The nonmagnetic layer has a thickness of 1.00 μm or less.
6. The magnetic recording medium according to claim 1, wherein The non-magnetic support further has a back coating layer containing non-magnetic powder on a surface side opposite to a surface side having the non-magnetic layer and the magnetic layer.
7. The magnetic recording medium according to claim 1, wherein The magnetic recording medium is a magnetic tape.
8. The magnetic recording medium according to claim 1, wherein In a cross-sectional image obtained by scanning electron microscope, the porosity of the non-magnetic layer is 10.0% or less. The non-magnetic layer contains 50.0 mass % or more of carbon black based on the total amount of the non-magnetic powder. The thickness of the non-magnetic layer is less than 1.00 μm, The non-magnetic support further has a back coating layer containing non-magnetic powder on the surface side opposite to the surface side having the non-magnetic layer and the magnetic layer, and The magnetic recording medium is a magnetic tape.
9. A magnetic tape cassette comprising the magnetic tape according to claim 7 or 8.
10. A magnetic recording and reproducing device comprising the magnetic recording medium according to any one of claims 1 to 8.
Citation Information
Patent Citations
Magnetic recording medium
JP1988090023A
Electric cleaner
JP1988130030A
Paper sheet feeding mechanism of character identification device
JP1988300031A
Production of magnetic paint
JP1989079274A
Production of kneading substance for magnetic coating
JP1989106338A